Assessments of gully erosion susceptibility in typical thick-layer Mollisol region of Northeast China - Binglong Wu; Fenli Zheng; Ximeng Xu; Yucheng Fu; Dennis C. Flanagan; Rong Li; Jiaqiong Zhang; Bin Wang; Jinxia Fu (Soil and Tillage Research, 2026)

Monsoon intensification as a driver of enhanced biogenic silica burial during the Bajocian cooling event in the western Yarlung Zangbo Suture Zone, southern Tibet - Xiaohui Cui; Xin Li; Jonathan C. Aitchison; Mei-Fu Zhou; Yichun Zhang; Jun Chen; Xuejin Wu; Xiru Li; Jiaqi Song; Hui Luo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A mechanically stable and kinetically optimized organic-inorganic hybrid SEI for ultra-long lifespan zinc metal anodes - Chenyi Cao; Dan Lu; Chao Li; Xin Tan; Tianci Li; Shoubin Zhou; Xueping Tang; Sean C. Smith; Zhao Fu; Hongjia Song; Yunya Liu; Xiangli Zhong; et al. (Chemical Engineering Journal, 2026)

Mid-Infrared spectroscopy for soil organic carbon estimation. Part I: Global review and meta-analysis - Tong Li; Anquan Xia; Ram C. Dalal; Sean Manning; Deeksha Beniwal; Zhihong Xu; Rajiv Pandey; Lizhen Cui; Songchao Chen; Peng Fu; Yushu Xia; Jinran Wu; et al. (Soil and Tillage Research, 2026)

Mid-infrared spectroscopy for soil organic carbon estimation. Part II: Evaluating preprocessing at global and national scales - Tong Li; Deeksha Beniwal; Ram C. Dalal; Sean Manning; Peng Fu; Anquan Xia; Jinran Wu; Qingyang Liu; Vilim Filipović; Georgios Tsiminis; Yash P. Dang (Soil and Tillage Research, 2026)

Investigation of the modal frequency response to spanwise ice accretion on a wing profile of unmanned aerial vehicle - Morakinyo J. Labiran; Olanrewaju M. Oyewola; Cheng-fu. Chen; Michael C. Hatfield (Next Research, 2026)

Climate-induced forest destabilization and shrub stabilization in Africa - Linhai Cheng; Qiang Tang; Nan Lu; Yafeng Wang; Changjia Li; Shuai Wang; Xiangyi Li; Phuping Sucharitakul; Yongzhe Chen; Zhihong Xu; Lindsay C. Stringer; Bojie Fu (Global and Planetary Change, 2026)

Zircon geochronology of the Gordonbrook Serpentinite: A fragment of mantle wedge within the New England Orogen, eastern Australia - George G.F. Murray; Solomon Buckman; Allen P. Nutman; Wanchese M. Saktura; Jonathan C. Aitchison; Vickie C. Bennett; Zhen Yan; Changlei Fu (Lithos, 2026)

Persistently high oxidative burden of PM2.5 amidst declining mass concentration: Evidence from long-term observation in Shanghai - Yue Huang; Yuankai Xie; Wei Zhang; Lu Xu; Ming Hu; Cheng Huang; Qingyan Fu; Steven J. Campbell; Gang I. Chen; David C. Green; Jialiang Feng; Shunyao Wang (Environmental Pollution, 2026)

Source Transition and Health Implication of PM2.5-Bound Metals: Multi-year High-resolution Observation in a Coastal Megacity - Yanjie Lei; Ming Hu; Yuankai Xie; Anja H. Tremper; Yue Liu; Lan Hong; Xin Cheng; Cheng Huang; Qingyan Fu; Jialiang Feng; David C. Green; Longhua Wu; et al. (Atmospheric Environment, 2026)

Constraints of integrated Fe and Li isotopes on fractional crystallization and fluid-magma interaction in the formation of unzoned Li-mineralized pegmatites - Shuaijie Liu; Mona-Liza C. Sirbescu; Bin Chen; Wenjing Li; Mei-Fu Zhou (Geochimica et Cosmochimica Acta, 2026)

Soil microbial communities and reactive oxygen species reshape MAOC-driven PAH accumulation under seasonal trade-offs between forest filtering and cold trapping - Weijie Liu; Xinli Xing; Ying Liu; Andrew J. Sweetman; Kevin C. Jones; Shizhen Zhao; Yanqi Ma; Yichen Lu; Qinglong Fu; Tianpeng Hu; Jiaquan Zhang; Shihua Qi (Journal of Hazardous Materials, 2026)

Immune divergence in rainbow trout lines selectively bred for F. psychrophilum resistance or susceptibility revealed by challenge with Weissella tructae - Gregory D. Wiens; Christopher C. Chadwick; Keira Osbourn; Qin Fu; Ross M. Reid; Travis Moreland; Timothy J. Welch; Timothy D. Leeds; David P. Marancik (Fish & Shellfish Immunology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Positive Atlantic Multidecadal Oscillation–La Niña synergy enhances recent East Asian dust activity via hydrothermal anomalies - Ruibo Zhao; Xiaoming Feng; Changjia Li; Yun Yang; Lindsay C. Stringer; Bojie Fu (Science Bulletin, 2026)

Multi-satellite derived data reveals spatiotemporal dynamics of carbon-water coupling and its drivers in tropical ecosystems - Xiang Wang; Zheng Fu; Philippe Ciais; Josep Peñuelas; Jingfeng Xiao; Xing Li; Xiangzhong Luo; Chi Chen; Haoyu Xia; Tao Zhou; Paul C. Stoy; Julia K. Green; et al. (Remote Sensing of Environment, 2026)

Late Ordovician arc-continent collision in the northernmost Tethyan-Ocean: Insights from detrital chromite and garnet geochemistry of the Koumenzi Formation in the Qilian Orogenic Belt - Hui Chen; Zhen Yan; Changlei Fu; Jonathan C. Aitchison (Global and Planetary Change, 2026)

Overexpression of DWARF14-LIKE2 in Arabidopsis thaliana alters multiple traits related to plant morphology and osmotic and salt stress tolerance - Xiaofan Nie; Liangliang Li; Chenbo Zhu; Kaixin Yang; Qingtian Li; Jiahe Fu; Minghui Xing; Mingming Wang; David C. Nelson; Xianzhong Feng; Jiuhai Zhao; Zhengwei Liang; et al. (Plant Cell Reports, 2026)

Paracremonium yunnanense (Sordariomycetes), a New Fungus From Swallow Cave in Yunnan Province, China - Xiang‐Fu Liu; Saowaluck Tibpromma; Kevin D. Hyde; Jayarama D. Bhat; Dong‐Qin Dai; Abdallah M. Elgorban; K. W. Thilini Chethana; Samantha C. Karunarathna (New Zealand Journal of Botany, 2026)
In this article, we describe a new cave‐associated fungus belonging to Nectriaceae (Hypocreales), collected from the air in Swallow Cave, Yunnan Province, China. Initial morphological observations confirmed that our collection exhibits characteristics typical of an acremonium‐like species. Phylogenetic analyses of the combined internal transcribed spacer (ITS), large subunit ribosomal RNA (LSU), and β‐tubulin ( TUB ) sequence dataset confirmed that our fungus forms an independent lineage within Paracremonium , sister to P. bendijkiorum , P. apiculatum , and P. variiforme . Based on morphology and multigene phylogeny, we describe our fungus as a new species, Paracremonium yunnanense . A comprehensive description, micrographs, and a phylogenetic tree showing the placement of the new species are provided. Moreover, our results contribute to understanding the genus Paracremonium and expand the knowledge of cave‐associated fungi in China.

GLS-YOLOv8n: a lightweight ‘Guiqi’ mango detection model via RGB-depth-thermal image fusion - Weihua Cao; Zhao Zhang; Zeping Wang; Ailin Wei; Qianfu Chen; C. Igathinathane; Fu Zhang; Mahmoud A. Abdelhamid; Dapeng Ye; Yiannis Ampatzidis (Computers and Electronics in Agriculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Effects of land-use change on soil total carbon pool: a meta-analysis - Zhuobing Ren; Changjia Li; Shuai Wang; Wenxin Zhou; Lindsay C. Stringer; Bojie Fu (Agriculture, Ecosystems & Environment, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Apatite cathodoluminescence and trace element geochemistry of Neoarchean and Paleoproterozoic iron oxide-copper-gold (IOCG) deposits of the Carajás domain, Brazil: implications for fluid evolution and metallogenesis - Raphael B. Hunger; Carolina P. N. Moreto; Roberto P. Xavier; Gustavo H. C. de Melo; Lena V. S. Monteiro; Gláucia N. Queiroga; Cristiano de C. Lana; Wang Liao; Xin-Fu Zhao; Poliana I. de F. Toledo (Mineralium Deposita, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

Biochar mitigates the suppressive effects of nitrogen deposition on soil methane uptake in a subtropical forest - Jiashu Zhou; Caixian Tang; Tony Vancov; Shenglei Fu; Yunying Fang; Tida Ge; Yanfei Dong; Yu Luo; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Agriculture, Ecosystems & Environment, 2026)

Event‐Specific Meteorological Drivers Shape Diverse Water‐Use Efficiency Trajectories Under Drought Propagation - Feng Li; Qinchuan Xin; Julia K. Green; Chuixiang Yi; Armen R. Kemanian; Steven A. Kannenberg; Paul C. Stoy; Yuting Yang; Huimin Lei; Yujiu Xiong; Zheng Fu (Global Change Biology, 2026)
Drought propagation from meteorological to soil drought marks a critical phase in regulating vegetation water–carbon dynamics, yet the response trajectories of water‐use efficiency (WUE) during these events remain poorly understood. Here, combining global flux tower observations with simulations from Earth System Models (ESMs), we quantified the spatiotemporal patterns of drought propagation characteristics, identified WUE response trajectories for characteristic‐specific droughts, and investigated their dominant drivers. We found that 58% of soil droughts follow meteorological droughts. Most sites experience drought propagation events with increasing intensity, faster propagation, and shorter intervals. Among all identifiable trajectories, nonmonotonic patterns account for approximately 60%. WUE response trajectories generally follow continuous and nonmonotonic patterns, dominated by a rise‐then‐fall pattern. This pattern reflects a process in which vegetation functions regulated by stomatal behavior are initially stressed and then partially recover. Intra‐site variability is extremely pronounced, mainly driven by event‐specific thermal factors such as air temperature and net radiation. ESMs reproduce broad site‐level prevalence of nonmonotonic patterns, but show discrepancies in the relative importance of drivers due to the coupling of different land surface models. These findings challenge the notion of fixed vegetation functional responses and highlight the dynamic variability of response trajectories in relation to event‐specific characteristics, and provide concrete diagnostics to guide model improvements.

Aggregate size mediates the stability and temperature sensitivity of soil organic carbon in response to decadal biochar and straw amendments - Yalan Chen; Yakov Kuzyakov; Qiwen Ma; Zhangliu Du; Ke Sun; Keqing Xiao; Xinru Liang; Yang Li; Yunxian Zhang; Xianqiang Lai; Wei Fu; Bo Gao; et al. (Soil Biology and Biochemistry, 2025)

Interpretable-generative machine learning approaches for predicting simultaneous removal of organic pollutants and heavy metals from water by adsorbent materials - Mudi Zhai; Zhaozhong Wu; Bomin Fu; Jingzhang Sun; Mohamad Sleiman; Frederic C. Meunier; Junsen Wang; Weijie Wang; Tianrun Wang; Haoran Duan; Zisheng Ai; Jose Luis Valverde; et al. (Journal of Cleaner Production, 2025)

Harnessing arbuscular mycorrhizal fungal communities for ecological restoration: a conceptual framework - Wei Fu; Tianyi Niu; Songlin Wu; Zhipeng Hao; Matthias C. Rillig; Baodong Chen (Soil Biology and Biochemistry, 2025)

P30-60 Grouping and assessment of chemicals for hazard and risk assessment by high content analysis using the zebrafish embryos as an alternative non-sentient animal model - S. Scholz; C. Zanini; A.-K. Koblitz; T. Möller; M.A. Aslam; G.C. Ajugwo; E. Chukwu; J. Colbourne; S. Kader; Q. Fu; N. Grasse; T. Reemtsma; et al. (Toxicology Letters, 2025)

P16-05 The zebrafish microbiome has the capacity to bioactivate PFOS precursor compounds - S. Gutsfeld; C. Wray; N. Schweiger; A. Röhrig; H. Paschke; Q. Fu; J. Kasmanas; S. Kader; U. da Rocha; T. Tal (Toxicology Letters, 2025)

Detecting Zone‐Type Thresholds for Soil Organic, Inorganic, and Total Carbon Pools in China's Drylands - Zhuobing Ren; Changjia Li; Bojie Fu; Wenxin Zhou; Xinli Chen; Shuai Wang; Lindsay C. Stringer (Global Change Biology, 2025)
Growing concerns about the accelerating global changes in drylands have intensified interest in understanding the impacts of diverse environmental factors on various soil carbon components, particularly their potential threshold effects, which may lead to abrupt nonlinear changes in both the quantity and composition of soil carbon. However, most research has predominantly focused on identifying key environmental drivers of either organic or inorganic carbon separately, often neglecting the presence and range of multiple critical thresholds. This study addresses this gap by analyzing extensive field data, including soil carbon measurements and ecosystem variables, collected across a ~4000 km transect in China's drylands. Utilizing a gradient forest model combined with threshold analyses, we assess the impacts of key drivers, including sand content, total nitrogen, aridity, and cation exchange capacity, on soil carbon pools. Our findings indicate that nitrogen content is the most influential factor for soil organic carbon, which was sensitive to low levels of nitrogen (0.07%–0.08%), with a slower response observed at higher levels. Aridity significantly affects both organic and inorganic carbon pools, with identified threshold zones for organic carbon at aridity levels of 0.48–0.52 and 0.75–0.85, and for inorganic carbon at 0.82–0.88. Threshold zones of sand content for total carbon are identified at lower levels and a wider range (51.4%–64.1% and 87.3%–88.1%), due to its negative effects on both organic and inorganic carbon, impacting 20% of the dryland area. Spatial variations in threshold effects revealed a trade‐off between nitrogen and pH in regulating soil total carbon. The combined threshold effects of climate warming and aridification may pose a greater threat to soil organic carbon in high‐latitude regions. This research enhances understanding of soil carbon dynamics in arid environments and offers novel approaches and insights for identifying thresholds in ecosystems that are increasingly at risk of reaching tipping points.

Upper Jurassic radiolarian assemblages and chert geochemistry of the Shiquanhe ophiolite, NW Tibet: Implications for the evolution of the Meso–Tethyan ocean - Xiaohui Cui; Yichun Zhang; Xin Li; Jonathan C. Aitchison; Mei-Fu Zhou; Qinggao Zeng; Guangying Ren; Hui Luo (Gondwana Research, 2025)

Antioxidative ceria nanoparticles protect acute lung injury-induced cognitive and emotional dysfunctions in mice - Yihan Liu; Shengyang Fu; Yan He; Xinwei Huang; Huikang Xie; Leyan Chen; Qihui Wu; Jialin C. Zheng; Weijun Cao (Chemical Engineering Journal, 2025)

Removal of fluoroquinolone antibiotic from wastewater based on immobilized metal affinity mechanism - L Zhao; B. Jia; M. He; H. Hu; Y. Guo; G. Fu; C. Hou; S. Gao; R. Li; X. Lv (International Journal of Environmental Science and Technology, 2025)

Limited Regulation of Canopy Water Use Efficiency by Stomatal Behavior Under Drought Propagation - Feng Li; Qinchuan Xin; Chuixiang Yi; Steven A. Kannenberg; Julia K. Green; Mirco Migliavacca; David J. P. Moore; Armen R. Kemanian; Pierre Gentine; Paul C. Stoy; Fangyue Zhang; Yujiu Xiong; et al. (Global Change Biology, 2025)
Water use efficiency (WUE) is a critical ecosystem function and a key indicator of vegetation responses to drought, yet its temporal trajectories and underlying drivers during drought propagation remain insufficiently understood. Here, we examined the trajectories, interdependencies and drivers of multidimensional WUE metrics and their components (gross primary production (GPP), evapotranspiration, transpiration (T), and canopy conductance (Gc)) using a conceptual drought propagation framework. We found that even though the carbon assimilation efficiency per stomata increases during drought, the canopy‐level WUE (represented by transpiration WUE (TWUE)) declines, indicating that stomatal regulation operates primarily at the leaf level and cannot offset the drought‐induced reduction in WUE at the canopy scale. A stronger dependence on T and TWUE indicates that the water–carbon trade‐off relationship of vegetation more inclines toward water transport than carbon assimilation. Gc fails to prevent the sharp decline in GPP during drought and has limited capacity to suppress T, as reflected by the reduction magnitude and the threshold (the turning point at which a component shifts from a normal to drought‐responsive state). The primary drivers of the water–carbon relationship under drought propagation include vapor pressure deficit and hydraulic traits. Among plant functional types, grasslands show the strongest water–carbon fluxes in response to drought, whereas evergreen broadleaf forests exhibit the weakest response. These findings refine our comprehensive understanding of multidimensional ecosystem functional dynamics under drought propagation and enlighten how the physiological response of vegetation to drought affects the carbon and water cycles.

Enhanced selective removal of lead from battery industry wastewater using MoS2@PbCO3 composite seeds via a nucleation crystallization pelleting process - Yadong Wang; Yabo Shang; Zhihao Fu; Keqian Li; Juan Shi; Lu Xu; Pengkang Jin; Xin Jin; Xiaochang C. Wang (Journal of Hazardous Materials, 2025)

Improving the climate signal of tree-ring blue intensity of sub-fossil wood using hydrogen peroxide: An example from the gulf of Alaska, USA - Wenshuo Zhao; Junpeng Fu; Nick Wiesenberg; Benjamin V. Gaglioti; Gregory C. Wiles (Dendrochronologia, 2025)

Living with bats: polyphasic approach reveals a new Fusarium species in Yunnan Province, China - Xiang‐Fu Liu; Saowaluck Tibpromma; Alice C. Hughes; Kevin D. Hyde; Abdallah M. Elgorban; Salim S. Al‐Rejaie; K. W. Thilini Chethana; Samantha C. Karunarathna (New Zealand Journal of Botany, 2025)
Bats are one of the most diverse mammal groups, with over 1400 species distributed across the planet, and they provide key ecological and economic services. In addition, bats provide an ideal habitat for fungal growth and harbour a high diversity of fungal species. Previous studies have described 423 fungal species associated with bats and bat carcasses. This paper describes a new fungal species, Fusarium rhinolophi, belonging to Nectriaceae, collected from bats in Mengla County, Xishuangbanna Dai Autonomous Prefecture, Yunnan Province, China. Phylogenetic analyses of the combined ITS, CAM , TEF‐1α , TUB , RPB1 , and RPB2 dataset confirmed that our fungus forms an independent lineage within the F. nisikadoi species complex. Thus, we describe our fungus as a new species of Fusarium based on morphology and molecular phylogeny. A description, phylogenetic tree showing species placement, and micrographs are provided.

Thyridium livistonae sp. nov. from Yunnan Province, China, with two new combinations - Jing Song; Samantha C. Karunarathna; Indunil C. Senanayake; Fu‐Qiang Yu (New Zealand Journal of Botany, 2025)
An ascomycetous fungus was collected and isolated from dead leaves of Livistona chinensis in Lincang City, Yunnan Province, China, and morphology and multi‐gene phylogenetic analyses of LSU, ITS, Actin , and β‐tub were carried out to identify it. The morphology and multigene phylogeny revealed that this fungus is a distinct species of Thyridium . Therefore, this fungus is described and introduced as Thyridium livistonae sp. nov. In addition, two new combinations T. hipposidericola and T. xishuangbannaense are proposed based on morphology and phylogeny for Phialemoniopsis hipposidericola Karun., Tibpromma & X.F. Liu and P. xishuangbannaensis Karun., Tibpromma & X.F. Liu respectively. A detailed description, illustrations, and phylogenetic results are provided for the new species and two new combinations.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Performance and mechanism of NiO/La-KTaO3 composite photocatalysts for UV degradation of isoamyl xanthate in synthetic flotation wastewater - X. Xu; L. Zhu; C. Chen; C. Luo; Z. Jin; Z. Sun; Z.T Fu (International Journal of Environmental Science and Technology, 2025)

Constraints of the paleowind directions on the paleogeography of the North China, South China and Tarim cratons during the Ediacaran Period - C. L. Hu; Z. Q. Lin; J. A. Quaye; X. B. Fu (Australian Journal of Earth Sciences, 2025)

Correction to: Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2025)

Increased Growth Temperatures Alter Arctic Plant Responses to Heat Wave and Drought - Marta Contreras‐Serrano; Neel Lindsby; Riikka Rinnan; Emma C. N. Duegaard; Eva Rosenqvist; Shouzhi Chen; Yongshuo H. Fu; Jing Tang (Global Change Biology, 2025)
Persistent warming and higher frequency of heat waves in the Arctic are causing alterations in Arctic vegetation and plant functionality, potentially redefining the role of the Arctic ecosystem. Vegetation influences atmospheric composition through exchanges of CO 2 and volatile organic compounds (VOCs), both processes exhibiting a strong response to temperature variations. However, our quantitative understanding of how increased temperatures interact with extreme weather events, namely heat waves and drought, to affect Arctic plant processes remains limited. Here, we measure phenology, photosynthesis, leaf fluorescence and VOC emissions from three widely distributed Arctic shrubs, Betula nana , Empetrum hermaphroditum and Salix spp., in response to future climate. We use state‐of‐the‐art climate chambers to test the effects of warmer growth temperatures on Arctic shrub responses to heat waves and drought. Our results show that increased growth temperatures advance leaf unfolding by 24 days in B. nana and 17 days in E. hermaphroditum , and increase VOC emissions across species. For B. nana , photosynthesis decreased by 42% during the heat wave and by 72% during drought. In contrast, Salix spp. and E. hermaphroditum experienced decreased photosynthesis only during drought, by 62% and 71%, respectively. The VOC emissions during the heat wave shifted toward a less diverse compound profile: acetaldehyde emissions increased for both control and warmed plants in all species, and isoprene emissions increased in Salix spp. Additionally, plants grown at higher temperatures exhibited a twofold increase in emissions compared to control plants during the heat wave, suggesting a higher temperature sensitivity of emissions. Our study indicates that warming and increasingly frequent extreme weather events will significantly impact Arctic plant phenology, photosynthesis and the diversity and rates of VOCs emitted into the atmosphere, contributing to modifying the regional climate.

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Drivers of forest productivity in two regions of the United States: Relative impacts of management and environmental variables - Hazhir Karimi; Michael Binford; William Kleindl; Gregory Starr; Bailey A. Murphy; Ankur R. Desai; Chiung-Shiuan Fu; Michael C. Dietze; Christina Staudhammer (Journal of Environmental Management, 2025)

Ground ozone rise during the 2022 shanghai lockdown caused by the unfavorable emission reduction ratio of nitrogen oxides and volatile organic compounds - Qian Wang; Yuewu Li; Fangqian Zhong; Wanqi Wu; Hongliang Zhang; Rong Wang; Yusen Duan; Qingyan Fu; Qing Li; Lin Wang; Shaocai Yu; Abdewahid Mellouki; et al. (Atmospheric Environment, 2025)

Peak flow in single-building lots in a residential areas with rainwater storage facilities in Taiwan - J C Fu; C M Tung (Journal of Earth System Science, 2024)

Antibiotic resistance at environmental multi-media interfaces through integrated genotype and phenotype analysis - Chen-Xi Fu; Chen Chen; Qian Xiang; Yi-Fei Wang; Lu Wang; Feng-Yuan Qi; Dong Zhu; Hong-Zhe Li; Li Cui; Wei-Li Hong; Matthias C. Rillig; Yong-Guan Zhu; et al. (Journal of Hazardous Materials, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Chemical classification of spherules recovered from the Pacific Ocean site of the CNEOS 2014-01-08 (IM1) bolide - A. Loeb; S.B. Jacobsen; R. Tagle; T. Adamson; S. Bergstrom; J. Cherston; R. Cloete; S. Cohen; L. Domine; H. Fu; C. Hoskinson; E. Hyung; et al. (Chemical Geology, 2024)

Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2024)

Maternal arsenic exposure modifies associations between arsenic, folate and arsenic metabolism gene variants, and spina bifida risk: A case‒control study in Bangladesh - Chih-Fu Wei; Gwen Tindula; Sudipta Kumer Mukherjee; Xingyan Wang; Sheikh Muhammad Ekramullah; D.M. Arman; Md Joynul Islam; Mubinul Azim; Asifur Rahman; Shamantha Afreen; Md Ziaddin; Benjamin C. Warf; et al. (Environmental Research, 2024)

MSH6-proficient crypt foci in MSH6 constitutional mismatch repair deficiency: reversion of a frameshifted coding microsatellite to its wild-type sequence - Jinru Shia; Francisco Sanchez-Vega; Stanley Cho; Jie-Fu Chen; Chin-Tung Chen; Umesh Bhanot; Nil Urganci; Canan Firat; Peter Ntiamoah; Raymond A. Isidro; Amitabh Srivastava; Martin R. Weiser; et al. (Familial Cancer, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Trend and inter-annual variability in regional climate models – Validation and hydrological implications in southeast Australia - Jin Teng; James C. Bennett; Steve Charles; Francis Chiew; Fei Ji; Nick Potter; Guobin Fu; Marcus Thatcher; Tomas Remenyi (Journal of Hydrology, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Taxonomy and phylogeny of endophytic Chaetomium (Chaetomiaceae) associated with mango ( Mangifera indica ) in Yunnan, China - Er-Fu Yang; Samantha C. Karunarathna; Abdallah M. Elgorban; Kasem Soytong; Itthayakorn Promputtha; Saowaluck Tibpromma (New Zealand Journal of Botany, 2024)

Eocene rhyolites in the Shanglaxiu-Xialaxiu area of north-eastern Qiangtang Block, Tibet: Partial melting of juvenile crust? - Yi-Wen Wei; Jun Wang; Qiang Wang; Bing-Zhang Wang; Andrew C. Kerr; Wu-Fu Li; Shan-Ping Li; Jin-Heng Liu; Chun-Tao Wang; Zi-Long Wang (Lithos, 2024)

Urine cadmium and urolithiasis: A systematic review and meta-analysis - Yuan-Hsin Chen; Chih-Fu Wei; Ya-Yun Cheng; Carol Mita; Chinh Lu Duc Hoang; Cheng-Kuan Lin; Yu-Tzu Chang; David C. Christiani (Environmental Research, 2024)

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

Preparation, pungency and bioactivity of gingerols from ginger ( Zingiber officinale Roscoe): a review - Yuge Gao; Yujia Lu; Na Zhang; Chibuike C. Udenigwe; Yuhao Zhang; Yu Fu (Critical Reviews in Food Science and Nutrition, 2024)

Customized plant microbiome engineering for food security - Maria Batool; Lilia C. Carvalhais; Brendan Fu; Peer M. Schenk (Trends in Plant Science, 2024)

Screening of representative rainfall event series for long-term hydrological performance evaluation of grassed swales - Feikai Yang; Dafang Fu; Chris Zevenbergen; Floris C. Boogaard; Rajendra Prasad Singh (Environmental Science and Pollution Research, 2024)

Partitioning of selenium from coal to fly ash: The key roles of Fe-bearing minerals and implications for Se potential recovery - Biao Fu; Guangyu Chen; Yijun Cao; James C. Hower; Yukun Huang; Yongda Huang; Luyao Chen; Guangqian Luo; Lu Dong; Hong Yao (Journal of Hazardous Materials, 2024)

Time-varying characteristics of saturated hydraulic conductivity in grassed swales based on the ensemble Kalman filter algorithm —A case study of two long-running swales in Netherlands - Feikai Yang; Dafang Fu; Chris Zevenbergen; Floris C. Boogaard; Rajendra Prasad Singh (Journal of Environmental Management, 2024)

Recognition and (semi-)quantitative analysis of REE-bearing minerals in coal using automated scanning electron microscopy - Biao Fu; Guorong Xu; James C. Hower; Yijun Cao; Yukun Huang; Liang Si; Li Xian; Guangqian Luo; Guijian Liu; Guangqing Hu; Hong Yao (International Journal of Coal Geology, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Spatially heterogeneous shifts in vegetation phenology induced by climate change threaten the integrity of the avian migration network - Jie Wei; Fei Xu; Ella F. Cole; Ben C. Sheldon; Willem F. de Boer; Ben Wielstra; Haohuan Fu; Peng Gong; Yali Si (Global Change Biology, 2024)
Phenological responses to climate change frequently vary among trophic levels, which can result in increasing asynchrony between the peak energy requirements of consumers and the availability of resources. Migratory birds use multiple habitats with seasonal food resources along migration flyways. Spatially heterogeneous climate change could cause the phenology of food availability along the migration flyway to become desynchronized. Such heterogeneous shifts in food phenology could pose a challenge to migratory birds by reducing their opportunity for food availability along the migration path and consequently influencing their survival and reproduction. We develop a novel graph‐based approach to quantify this problem and deploy it to evaluate the condition of the heterogeneous shifts in vegetation phenology for 16 migratory herbivorous waterfowl species in Asia. We show that climate change‐induced heterogeneous shifts in vegetation phenology could cause a 12% loss of migration network integrity on average across all study species. Species that winter at relatively lower latitudes are subjected to a higher loss of integrity in their migration network. These findings highlight the susceptibility of migratory species to climate change. Our proposed methodological framework could be applied to migratory species in general to yield an accurate assessment of the exposure under climate change and help to identify actions for biodiversity conservation in the face of climate‐related risks.

Effects of aridification on soil total carbon pools in China's drylands - Zhuobing Ren; Changjia Li; Bojie Fu; Shuai Wang; Lindsay C. Stringer (Global Change Biology, 2024)
Drylands are important carbon pools and are highly vulnerable to climate change, particularly in the context of increasing aridity. However, there has been limited research on the effects of aridification on soil total carbon including soil organic carbon and soil inorganic carbon, which hinders comprehensive understanding and projection of soil carbon dynamics in drylands. To determine the response of soil total carbon to aridification, and to understand how aridification drives soil total carbon variation along the aridity gradient through different ecosystem attributes, we measured soil organic carbon, inorganic carbon and total carbon across a ~4000 km aridity gradient in the drylands of northern China. Distribution patterns of organic carbon, inorganic carbon, and total carbon at different sites along the aridity gradient were analyzed. Results showed that soil organic carbon and inorganic carbon had a complementary relationship, that is, an increase in soil inorganic carbon positively compensated for the decrease in organic carbon in semiarid to hyperarid regions. Soil total carbon exhibited a nonlinear change with increasing aridity, and the effect of aridity on total carbon shifted from negative to positive at an aridity level of 0.71. In less arid regions, aridification leads to a decrease in total carbon, mainly through a decrease in organic carbon, whereas in more arid regions, aridification promotes an increase in inorganic carbon and thus an increase in total carbon. Our study highlights the importance of soil inorganic carbon to total carbon and the different effects of aridity on soil carbon pools in drylands. Soil total carbon needs to be considered when developing measures to conserve the terrestrial carbon sink.

Functions and values of sulfated polysaccharides from seaweed - D. P. Nagahawatta; N. M. Liyanage; Thilina U. Jayawardena; Fengqi Yang; H. H. A. C. K. Jayawardena; M. J. M. S. Kurera; Fahe Wang; Xiaoting Fu; You-Jin Jeon (Algae, 2023)
Sulfated polysaccharides (SPs) isolated from seaweed have emerged as remarkable bioactive compounds with a wide spectrum of biological activities and have substantial value in the scientific and industrial domains. The current study explores the diverse biological activities of SPs and their relationship with their structures. This aids in an in-depth examination of the multifaceted biological activities of SPs, including anticoagulant, anti-inflammatory, antiviral, antioxidant, and immunomodulatory properties, which underpin their potential health benefits. Furthermore, the current study explores the complicated properties of SPs, with their extraction methodologies and techniques for precise characterization. Elucidation of the commercial significance of SPs derived from brown, red, and green seaweed by highlighting their potential applications has emphasized their importance in human well-being. Further, this review emphasizes the challenges needed to overcome research and industrial innovations for SPs. Collaboration among researchers, industry stakeholders, and regulatory authorities can overcome these challenges and elevate the potential of SPs to revolutionize industries such as pharmaceuticals, cosmeceuticals, food, and biotechnology.

Detection and attribution of an anomaly in terrestrial photosynthesis in Europe during the COVID-19 lockdown - Angela Che Ing Tang; Christophe R. Flechard; Nicola Arriga; Dario Papale; Paul C. Stoy; Nina Buchmann; Matthias Cuntz; John Douros; Silvano Fares; Alexander Knohl; Ladislav Šigut; Guillaume Simioni; et al. (Science of The Total Environment, 2023)

16s-RNA sequencing analysis of the influence of UV radiation on the metabolic pathways of pollutants in the A2O process - Y. W. Li; J. H. You; Y. C. Zong; J. Wang; C. H. Fu (International Journal of Environmental Science and Technology, 2023)

Learning-Based personal models for joint optimization of thermal comfort and energy consumption in flexible workplaces - Min Deng; Bo Fu; Carol C. Menassa; Vineet R. Kamat (Energy and Buildings, 2023)

Source partitioning using phosphate oxygen isotopes and multiple models in a large catchment - Ziteng Wang; Liyan Tian; Changqiu Zhao; Chenjun Du; Jun Zhang; Fuhong Sun; Teklit Zerizghi Tekleab; Rongfei Wei; Pingqing Fu; Daren C. Gooddy; Qingjun Guo (Water Research, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Geochronology and petrogenesis of the early Silurian Zeluo mafic-ultramafic intrusion, eastern Tibet: implications for the tectonic setting and evolution of the eastern Proto-Tethys Ocean - Hang Zhou; Wenxiao Zhou; Ernest Chi Fru; Thomas C. Sheldrick; Haiquan Li; Bo Huang; Dong Fu; Yadong Xu (International Geology Review, 2023)

Constitutively Synergistic Multiagent Drug Formulations Targeting MERTK, FLT3, and BCL-2 for Treatment of AML - James M. Kelvin; Juhi Jain; Aashis Thapa; Min Qui; Lacey A. Birnbaum; Samuel G. Moore; Henry Zecca; Ryan J. Summers; Jeffrey M. Switchenko; Emma Costanza; Biaggio Uricoli; Xiaodong Wang; et al. (Pharmaceutical Research, 2023)

Hydrothermal conversion of hydrocarbons to heterocyclic compounds by geological supercritical CO2 volatiles - Quanyou Liu; Huiyuan Xu; Zhijun Jin; Dongya Zhu; Qingqiang Meng; Xiaoqi Wu; Qi Fu; Simon C. George (Science Bulletin, 2023)

Cerebrospinal fluid levels of 5-HIAA and dopamine in people with HIV and depression - Rong Fu; Hyder Jinnah; J. Lucas Mckay; Andrew H. Miller; Jennifer C. Felger; Eugene W. Farber; Sanjay Sharma; Neil Whicker; Raeanne C. Moore; Donald Franklin; Scott L. Letendre; Albert M. Anderson (Journal of NeuroVirology, 2023)

FGF21 via mitochondrial lipid oxidation promotes physiological vascularization in a mouse model of Phase I ROP - Zhongjie Fu; Pia Lundgren; Aldina Pivodic; Hitomi Yagi; Jarrod C. Harman; Jay Yang; Minji Ko; Katherine Neilsen; Saswata Talukdar; Ann Hellström; Lois E. H. Smith (Angiogenesis, 2023)
Hyperglycemia in early postnatal life of preterm infants with incompletely vascularized retinas is associated with increased risk of potentially blinding neovascular retinopathy of prematurity (ROP). Neovascular ROP (Phase II ROP) is a compensatory but ultimately pathological response to the suppression of physiological postnatal retinal vascular development (Phase I ROP). Hyperglycemia in neonatal mice which suppresses physiological retinal vascular growth is associated with decreased expression of systemic and retinal fibroblast growth factor 21 (FGF21). FGF21 administration promoted and FGF21 deficiency suppressed the physiological retinal vessel growth. FGF21 increased serum adiponectin (APN) levels and loss of APN abolished FGF21 promotion of physiological retinal vascular development. Blocking mitochondrial fatty acid oxidation also abolished FGF21 protection against delayed physiological retinal vessel growth. Clinically, preterm infants developing severe neovascular ROP (versus non-severe ROP) had a lower total lipid intake with more parenteral and less enteral during the first 4 weeks of life. Our data suggest that increasing FGF21 levels in the presence of adequate enteral lipids may help prevent Phase I retinopathy (and therefore prevent neovascular disease).

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

The spongiform tissue in Strumigenys ants contains exocrine glands - Chu Wang; Fu-Ya Chung; Chung-Chi Lin; Joshua C. Gibson; Sara McGuire; Andrew V. Suarez; Johan Billen (Arthropod Structure & Development, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

The heterogeneous response of martian meteorite Allan Hills 84001 to planar shock - Thomas L. North; Gareth S. Collins; Thomas M. Davison; Adrian R. Muxworthy; Sarah C. Steele; Roger R. Fu (Icarus, 2023)

Ecophysiological and genomic analyses of a representative isolate of highly abundant Bacillus cereus strains in contaminated subsurface sediments - Jennifer L. Goff; Elizabeth G. Szink; Michael P. Thorgersen; Andrew D. Putt; Yupeng Fan; Lauren M. Lui; Torben N. Nielsen; Kristopher A. Hunt; Jonathan P. Michael; Yajiao Wang; Daliang Ning; Ying Fu; et al. (Environmental Microbiology, 2022)
Bacillus cereus strain CPT56D‐587‐MTF (CPTF) was isolated from the highly contaminated Oak Ridge Reservation (ORR) subsurface. This site is contaminated with high levels of nitric acid and multiple heavy metals. Amplicon sequencing of the 16S rRNA genes (V4 region) in sediment from this area revealed an amplicon sequence variant (ASV) with 100% identity to the CPTF 16S rRNA sequence. Notably, this CPTF‐matching ASV had the highest relative abundance in this community survey, with a median relative abundance of 3.77% and comprised 20%–40% of reads in some samples. Pangenomic analysis revealed that strain CPTF has expanded genomic content compared to other B. cereus species—largely due to plasmid acquisition and expansion of transposable elements. This suggests that these features are important for rapid adaptation to native environmental stressors. We connected genotype to phenotype in the context of the unique geochemistry of the site. These analyses revealed that certain genes (e.g. nitrate reductase, heavy metal efflux pumps) that allow this strain to successfully occupy the geochemically heterogenous microniches of its native site are characteristic of the B. cereus species while others such as acid tolerance are mobile genetic element associated and are generally unique to strain CPTF.

Controlling Hydraulic Fracture Growth Through Precise Vertical Placement of Lateral Wells: Insights from HFTS Experiment and Numerical Validation - W. Fu; J. P. Morris; C. S. Sherman; P. Fu; J. Huang (Rock Mechanics and Rock Engineering, 2022)

Field engineering application of agricultural farmland surface runoff pollution treatment by combined bioreactor and constructed wetlands - H. Luo; X. Li; Y. Chen; X. Liu; K. Zhang; X. Fu; B. Jiang; R. Xue; J. Yang; M. Li; X. Li; W. Chen; et al. (International Journal of Environmental Science and Technology, 2022)

Long-lived dacitic magmatic systems and recharge dynamics in the Jemez Mountains volcanic field, western USA - Jie Wu; Michael C. Rowe; Shane J. Cronin; John A. Wolff; Bin Fu (Contributions to Mineralogy and Petrology, 2022)
We examine the connected history of dacite-dominant volcanic rocks of the Tschicoma Formation, erupted between 5.5 and 2 Ma from the Jemez Mountains volcanic field, western USA. Zircon samples from two separate eruptions have continuous SHRIMP U–Pb age spectra spanning 0.84–1.08 Myr duration (3.12–3.96 Ma and 3.50–4.58 Ma, respectively), following an episode of zircon crystallization 0.28–0.50 Myr earlier (at 4.46 Ma and 4.86 Ma, respectively). Zircon chemical variations, as well as ubiquitous resorption textures that commonly show large core-rim age differences (up to 720–740 kyr), suggest that they grew in separate melt lenses. Zircons were likely stored at near-solidus or even sub-solidus conditions after crystallization, but may have been reactivated in response to at least four major magma recharge events every 300–400 kyr and smaller events in between. A cycle of zircon dissolution (from heating), recrystallization (during cooling), and storage repeated in different locations in the Tschicoma mush system throughout its lifespan; each recharge-induced heating stage may last for several hundred to more than a thousand years based on calculations of zircon dissolution. We envisage the melt lenses to be distributed in a crystal mush zone, coalescing into a single magma batch as magma recharge occurs shortly before eruption. Once active, increasing magma supply rates may trigger large-scale partial melting of the pre-existing mush and caldera-forming eruptions.

Surrogate Models in Rock and Soil Mechanics: Integrating Numerical Modeling and Machine Learning - J. K. Furtney; C. Thielsen; W. Fu; R. Le Goc (Rock Mechanics and Rock Engineering, 2022)

Failure modes of slope stabilized by frame beam with prestressed anchors - J. J. Zhang; J. Y. Niu; X. Fu; L. C. Cao; S. J. Yan (European Journal of Environmental and Civil Engineering, 2022)

Cycle Length Evaluation in Persistent Atrial Fibrillation Using Kernel Density Estimation to Identify Transient and Stable Rapid Atrial Activity - Szabolcs Z. Nagy; Patrick Kasi; Valtino X. Afonso; Nathaniel Bird; Brian Pederson; Ian E. Mann; Steven Kim; Nicholas W. F. Linton; David C. Lefroy; Zachary I. Whinnett; Fu Siong Ng; Michael Koa-Wing; et al. (Cardiovascular Engineering and Technology, 2022)
Purpose Left atrial (LA) rapid AF activity has been shown to co-localise with areas of successful atrial fibrillation termination by catheter ablation. We describe a technique that identifies rapid and regular activity. Methods Eight-second AF electrograms were recorded from LA regions during ablation for psAF. Local activation was annotated manually on bipolar signals and where these were of poor quality, we inspected unipolar signals. Dominant cycle length (DCL) was calculated from annotation pairs representing a single activation interval, using a probability density function (PDF) with kernel density estimation. Cumulative annotation duration compared to total segment length defined electrogram quality. DCL results were compared to dominant frequency (DF) and averaging. Results In total 507 8 s AF segments were analysed from 7 patients. Spearman’s correlation coefficient was 0.758 between independent annotators ( P < 0.001), 0.837–0.94 between 8 s and ≥ 4 s segments ( P < 0.001), 0.541 between DCL and DF ( P < 0.001), and 0.79 between DCL and averaging ( P < 0.001). Poorer segment organization gave greater errors between DCL and DF. Conclusion DCL identifies rapid atrial activity that may represent psAF drivers. This study uses DCL as a tool to evaluate the dynamic, patient specific properties of psAF by identifying rapid and regular activity. If automated, this technique could rapidly identify areas for ablation in psAF.

Uncovering the critical soil moisture thresholds of plant water stress for European ecosystems - Zheng Fu; Philippe Ciais; David Makowski; Ana Bastos; Paul C. Stoy; Andreas Ibrom; Alexander Knohl; Mirco Migliavacca; Matthias Cuntz; Ladislav Šigut; Matthias Peichl; Denis Loustau; et al. (Global Change Biology, 2022)
Understanding the critical soil moisture (SM) threshold (θ crit ) of plant water stress and land surface energy partitioning is a basis to evaluate drought impacts and improve models for predicting future ecosystem condition and climate. Quantifying the θ crit across biomes and climates is challenging because observations of surface energy fluxes and SM remain sparse. Here, we used the latest database of eddy covariance measurements to estimate θ crit across Europe by evaluating evaporative fraction (EF)‐SM relationships and investigating the covariance between vapor pressure deficit (VPD) and gross primary production (GPP) during SM dry‐down periods. We found that the θ crit and soil matric potential threshold in Europe are 16.5% and −0.7 MPa, respectively. Surface energy partitioning characteristics varied among different vegetation types; EF in savannas had the highest sensitivities to SM in water‐limited stage, and the lowest in forests. The sign of the covariance between daily VPD and GPP consistently changed from positive to negative during dry‐down across all sites when EF shifted from relatively high to low values. This sign of the covariance changed after longer period of SM decline in forests than in grasslands and savannas. Estimated θ crit from the VPD–GPP covariance method match well with the EF–SM method, showing this covariance method can be used to detect the θ crit . We further found that soil texture dominates the spatial variability of θ crit while shortwave radiation and VPD are the major drivers in determining the spatial pattern of EF sensitivities. Our results highlight for the first time that the sign change of the covariance between daily VPD and GPP can be used as an indicator of how ecosystems transition from energy to SM limitation. We also characterized the corresponding θ crit and its drivers across diverse ecosystems in Europe, an essential variable to improve the representation of water stress in land surface models.

Documenting pollinators, floral hosts, and plant–pollinator interactions in U.S. P acific N orthwest agroecosystems - Elias H. Bloom; Elisabeth C. Oeller; Rachel L. Olsson; Matthew R. Brousil; Robert N. Schaeffer; Saumik Basu; Zhen Fu; David W. Crowder (Ecology, 2022)
The abundance and diversity of pollinator populations are in global decline. Managed pollinator species, like honey bees, and wild species are key ecosystem service providers in both natural and managed agroecosystems. However, relatively few studies have exhaustively characterized pollinator populations in diverse agroecosystems over multiple years, while also thoroughly documenting plant–pollinator interactions. Yet, such studies are needed to fulfill the national pollinator protection plans that have been released by the United States and other nations. Our research is among the first studies to respond to these directives by systematically documenting bee and plant biodiversity, bee–plant interactions, and bee‐mediated pollen movement in farming systems of the Pacific Northwest, USA. Our data provides insight into the processes mediating pollinator and plant community assembly, persistence, and resilience across landscapes with variable crop and landscape diversity and agroecosystem management practices. These data will also contribute to the development of a United States pollinator database, supporting the United States' plan to promote pollinators. With few publicly available data sets that systematically take account of agroecosystem practices, plant populations, and pollinators, our research will provide future users the means to conduct synesthetic studies of pollinators and ecosystem function in a period of rapid and global pollinator declines. There are no copyright or proprietary restrictions for research or teaching purposes. Usage of the data set must be cited.

Aspirin use and prostate tumor angiogenesis - Benjamin C. Fu; Kai Wang; Lorelei A. Mucci; Steven K. Clinton; Edward L. Giovannucci (Cancer Causes & Control, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Can the mechanoreceptional setae of a feeding‐current feeding copepod detect hydrodynamic disturbance induced by entrained free‐floating prey? - Xinhui Shen; Xin Yao; Marcos; Henry C. Fu (Limnology and Oceanography, 2021)
Copepods that catch prey using feeding currents beat their cephalic appendages to generate flow entrainment, and detect the presence of nearby prey through the mechanoreceptional setae on the antennules and other appendages. It remains unclear whether the feeding current can be used by the copepod to gain information about its surroundings by sensing when the current is disturbed by nearby particles. In this article, we present a numerical model to address how much the presence of free‐floating prey can alter the feeding current velocity field, and how these prey‐induced disturbances modify setal deformation patterns. We prescribe the beating strokes of the feeding appendages, and quantify the changes in the bending flows across the setae and setal deformations due to the prey entrainment. We find that, first, the seta bends more due to the time‐averaged velocity component of the feeding current, while filtering out the oscillatory component. Second, 100 μ m diameter free‐floating prey do not induce any noticeable change in deformations of the proximal and distal setae unless they are less than 10 or 5.5 prey radii from the antennules, respectively. Larger prey cause bigger flow disturbances than small prey, which are expected to be even harder to detect. Last, if setae are responsive to changes in deformation relative to the deformations in the absence of prey, the distal seta may have long‐ranged sensitivity to assist in detection of prey near the proximal seta, but if setae are responsive to absolute changes in deformation, both setae have very short‐ranged sensitivity.

The Santa Lúcia Cu-Au deposit, Carajás Mineral Province, Brazil: a Neoarchean (2.68 Ga) member of the granite-related copper-gold systems of Carajás - Raphael B. Hunger; Gustavo H. C. de Melo; Roberto P. Xavier; Carolina P. N. Moreto; Cristina Talavera; Zhi-Kun Su; Xin-Fu Zhao (Mineralium Deposita, 2021)

Delineating the organization of projection neuron subsets in primary visual cortex with multiple fluorescent rabies virus tracing - Liang Li; Yajie Tang; Leqiang Sun; Jinsong Yu; Siheng Zhang; Hui Gong; Hannah C. Webber; Xiaoyu Zhang; Zhe Hu; Xiangning Li; Khaista Rahman; Xiangwei Shi; et al. (Brain Structure and Function, 2021)

Nano-selenium Supplementation Increases Selenoprotein (Sel) Gene Expression Profiles and Milk Selenium Concentration in Lactating Dairy Cows - Liqiang Han; Kun Pang; Tong Fu; Clive J. C. Phillips; Tengyun Gao (Biological Trace Element Research, 2021)
Supplementation with selenium is common for dairy cows, but the importance of selenium source is not clear. This study aimed to compare nano-selenium (Nano-Se) and sodium selenite supplements for dairy cows on lactation performance, milk Se levels and selenoprotein (Sel) gene expression. Twelve multiparous Holstein cows were randomly divided into two groups: a control group fed a basal diet plus 0.30 mg Se/kg of DM as sodium selenite or Nano-Se for 30 days. Dry matter intake, milk yield and composition were not affected by dietary Se source ( P > 0.05); however, the milk total Se levels and milk glutathione peroxidase (GSH-Px) activities were higher with Nano-Se supplementation than sodium selenite ( P < 0.05). At the end of the experiment, Nano-Se supplementation significantly increased plasma Se levels and GSH-Px activity, compared with the sodium selenite supplement. The mRNA expression levels of glutathione peroxidase 1, 2 and 4; thioredoxin reductase 2 and 3; and selenoproteins W, T, K and F were markedly upregulated ( P < 0.05) in the mammary gland of the Nano-Se group. Thus, the source of selenium plays an important role in the antioxidant status and in particular the Sel gene expression in the mammary glands of dairy cows, both being stimulated by nano sources.

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Diversity in the population of Fusarium graminearum isolated from wheat and corn in Alberta, Canada - Hafiz Ahmed; Qixing Zhou; Kher Zahr; Yalong Yang; Heting Fu; Alian Sarkes; Yingli Wang; Krista Zuzak; David Feindel; Greg C. Daniels; Michael W. Harding; Jie Feng (Journal of Plant Diseases and Protection, 2020)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Specific genes and sequence variation in pathotype 7 of the clubroot pathogen Plasmodiophora brassicae - H. Yang; J. Zheng; Y. D. Fu; Y. H. Zhang; C. L. Yi; C. Jin; Y. Huang; Wenming Wang (European Journal of Plant Pathology, 2020)

How the bending mechanics of setae modulate hydrodynamic sensing in copepods - Xinhui Shen; Marcos; Henry C. Fu (Limnology and Oceanography, 2020)
Copepods sense the hydrodynamic disturbances induced by swimming planktonic prey, potential mates, and predators through the bending of setae on their first antennae and other appendages. While the flows induced by these sources have been studied and are crucial for the mechanoreception of copepods, there is little knowledge on how these flows cause the deformation of the copepod's mechanoreceptional seta. In this article, we present a mechanical model to address how the mechanics of setal deformation by hydrodynamic signals determines the sensing capabilities of copepods. We represent a generic flow around a copepod as a combination of a uniform plus shear flow, and demonstrate that the detailed geometry of the first antenna has non‐negligible effects on the flow profile across the seta. We then proceed to evaluate the setal deformations induced by such a flow oscillating at frequencies relevant for copepod sensing, and find that lower frequency signals lead to larger setal bending and are more easily detected. We investigate the effects of setal length, signal amplitude, and signal frequency on setal bending. Finally, we investigate the response time of setal bending to hydrodynamic signals, and find short response time consistent with the rapid behavioral and neurological response of copepods.

The acclimation of leaf photosynthesis of wheat and rice to seasonal temperature changes in T‐FACE environments - Chuang Cai; Gang Li; Lijun Di; Yunjie Ding; Lin Fu; Xuanhe Guo; Paul C. Struik; Genxing Pan; Haozheng Li; Weiping Chen; Weihong Luo; Xinyou Yin (Global Change Biology, 2020)
Crops show considerable capacity to adjust their photosynthetic characteristics to seasonal changes in temperature. However, how photosynthesis acclimates to changes in seasonal temperature under future climate conditions has not been revealed. We measured leaf photosynthesis ( A n ) of wheat ( Triticum aestivum L.) and rice ( Oryza sativa L.) grown under four combinations of two levels of CO 2 (ambient and enriched up to 500 µmol/mol) and two levels of canopy temperature (ambient and increased by 1.5–2.0°C) in temperature by free‐air CO 2 enrichment (T‐FACE) systems. Parameters of a biochemical C 3 ‐photosynthesis model and of a stomatal conductance ( g s ) model were estimated for the four conditions and for several crop stages. Some biochemical parameters related to electron transport and most g s parameters showed acclimation to seasonal growth temperature in both crops. The acclimation response did not differ much between wheat and rice, nor among the four treatments of the T‐FACE systems, when the difference in the seasonal growth temperature was accounted for. The relationships between biochemical parameters and leaf nitrogen content were consistent across leaf ranks, developmental stages, and treatment conditions. The acclimation had a strong impact on g s model parameters: when parameter values of a particular stage were used, the model failed to correctly estimate g s values of other stages. Further analysis using the coupled g s –biochemical photosynthesis model showed that ignoring the acclimation effect did not result in critical errors in estimating leaf photosynthesis under future climate, as long as parameter values were measured or derived from data obtained before flowering.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Maximum carbon uptake rate dominates the interannual variability of global net ecosystem exchange - Zheng Fu; Paul C. Stoy; Benjamin Poulter; Tobias Gerken; Zhen Zhang; Guta Wakbulcho; Shuli Niu (Global Change Biology, 2019)
Terrestrial ecosystems contribute most of the interannual variability (IAV) in atmospheric carbon dioxide (CO 2 ) concentrations, but processes driving the IAV of net ecosystem CO 2 exchange (NEE) remain elusive. For a predictive understanding of the global C cycle, it is imperative to identify indicators associated with ecological processes that determine the IAV of NEE. Here, we decompose the annual NEE of global terrestrial ecosystems into their phenological and physiological components, namely maximum carbon uptake (MCU) and release (MCR), the carbon uptake period (CUP), and two parameters, α and β, that describe the ratio between actual versus hypothetical maximum C sink and source, respectively. Using long‐term observed NEE from 66 eddy covariance sites and global products derived from FLUXNET observations, we found that the IAV of NEE is determined predominately by MCU at the global scale, which explains 48% of the IAV of NEE on average while α, CUP, β, and MCR explain 14%, 25%, 2%, and 8%, respectively. These patterns differ in water‐limited ecosystems versus temperature‐ and radiation‐limited ecosystems; 31% of the IAV of NEE is determined by the IAV of CUP in water‐limited ecosystems, and 60% of the IAV of NEE is determined by the IAV of MCU in temperature‐ and radiation‐limited ecosystems. The Lund‐Potsdam‐Jena (LPJ) model and the Multi‐scale Synthesis and Terrestrial Model Inter‐comparison Project (MsTMIP) models underestimate the contribution of MCU to the IAV of NEE by about 18% on average, and overestimate the contribution of CUP by about 25%. This study provides a new perspective on the proximate causes of the IAV of NEE, which suggest that capturing the variability of MCU is critical for modeling the IAV of NEE across most of the global land surface.

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Early Cambrian Muli arc–ophiolite complex: a relic of the Proto-Tethys oceanic lithosphere in the Qilian Orogen, NW China - Zhen Yan; Changlei Fu; Jonathan C. Aitchison; Manlan Niu; Solomon Buckman; Bo Cao (International Journal of Earth Sciences, 2019)

Sequence stratigraphy and Quaternary depositional systems in the Sanhu area of the Qaidam Basin, northwest China - Z. Liu; S. Fu; H. C. Jia; J. X. Tian; Y. H. Chen; C. Y. Dong (Australian Journal of Earth Sciences, 2019)

Physiological responses of the freshwater N 2 ‐fixing cyanobacterium Raphidiopsis raciborskii to Fe and N availabilities - Qing‐Long Fu; Anna C. Y. Yeung; Manabu Fujii; Brett A. Neilan; T. David Waite (Environmental Microbiology, 2019)
Summary The cyanobacterium Raphidiopsis raciborskii is of environmental and social concern in view of its toxicity, bloom‐forming characteristics and increasingly widespread occurrence. However, while availability of macronutrients and micronutrients such as N and Fe are critically important for the growth and metabolism of this organism, the physiological response of toxic and non‐toxic strains of R. raciborskii to varying Fe and N availabilities remains unclear. By determining physiological parameters as a function of Fe and N availability, we demonstrate that R. raciborskii growth and N 2 ‐fixing activity are facilitated at higher Fe availability under N 2 ‐limited conditions with faster growth of the CS‐506 (cylindrospermopsin‐producing) strain compared with that of CS‐509 (the non‐toxic) strain. Radiolabelled Fe uptake assays indicated that R. raciborskii acclimated under Fe‐limited conditions acquires Fe at significantly higher rates than under Fe replete conditions, principally via unchelated Fe(II) generated as a result of photoreduction of complexed Fe(III). While N 2 ‐fixation of both strains occurred during both day and night, the CS‐506 strain overall exhibited higher N 2 ‐fixing and Fe uptake rates than the CS‐509 strain under N‐deficient and Fe‐limited conditions. The findings of this study highlight that Fe availability is of significance for the ecological advantage of CS‐506 over CS‐509 in N‐deficient freshwaters.

Real-World Variability in the Prediction of Intracranial Aneurysm Wall Shear Stress: The 2015 International Aneurysm CFD Challenge - Kristian Valen-Sendstad; Aslak W. Bergersen; Yuji Shimogonya; Leonid Goubergrits; Jan Bruening; Jordi Pallares; Salvatore Cito; Senol Piskin; Kerem Pekkan; Arjan J. Geers; Ignacio Larrabide; Saikiran Rapaka; et al. (Cardiovascular Engineering and Technology, 2018)

Different CO2 acclimation strategies in juvenile and mature leaves of Ottelia alismoides - Wen Min Huang; Hui Shao; Si Ning Zhou; Qin Zhou; Wen Long Fu; Ting Zhang; Hong Sheng Jiang; Wei Li; Brigitte Gontero; Stephen C. Maberly (Photosynthesis Research, 2018)

Isometric strength of the hip abductors and external rotators in athletes with and without patellar tendinopathy - Z. J. Zhang; W. C. Lee; G. Y. F. Ng; S. N. Fu (European Journal of Applied Physiology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Application of the Hybrid Artificial Neural Network Coupled with Rolling Mechanism and Grey Model Algorithms for Streamflow Forecasting Over Multiple Time Horizons - Zaher Mundher Yaseen; Minglei Fu; Chen Wang; Wan Hanna Melini Wan Mohtar; Ravinesh C. Deo; Ahmed El-shafie (Water Resources Management, 2018)

On the ratio of intercellular to ambient CO2 (c i/c a) derived from ecosystem flux - Zheng-Hong Tan; Zhi-Xiang Wu; Alice C. Hughes; Douglas Schaefer; Jiye Zeng; Guo-Yu Lan; Chuang Yang; Zhong-Liang Tao; Bang-Qian Chen; Yao-Hua Tian; Liang Song; Muhammad Tahir Jatoi; et al. (International Journal of Biometeorology, 2017)

Interannual variability of ecosystem carbon exchange: From observation to prediction - Shuli Niu; Zheng Fu; Yiqi Luo; Paul C. Stoy; Trevor F. Keenan; Benjamin Poulter; Leiming Zhang; Shilong Piao; Xuhui Zhou; Han Zheng; Jiayin Han; Qiufeng Wang; et al. (Global Ecology and Biogeography, 2017)
Aim Terrestrial ecosystems have sequestered, on average, the equivalent of 30% of anthropogenic carbon (C) emissions during the past decades, but annual sequestration varies from year to year. For effective C management, it is imperative to develop a predictive understanding of the interannual variability (IAV) of terrestrial net ecosystem C exchange (NEE). Location Global terrestrial ecosystems. Methods We conducted a comprehensive review to examine the IAV of NEE at global, regional and ecosystem scales. Then we outlined a conceptual framework for understanding how anomalies in climate factors impact ecological processes of C cycling and thus influence the IAV of NEE through biogeochemical regulation. Results The phenomenon of IAV in land NEE has been ubiquitously observed at global, regional and ecosystem scales. Global IAV is often attributable to either tropical or semi‐arid regions, or to some combination thereof, which is still under debate. Previous studies focus on identifying climate factors as driving forces of IAV, whereas biological mechanisms underlying the IAV of ecosystem NEE are less clear. We found that climate anomalies affect the IAV of NEE primarily through their differential impacts on ecosystem C uptake and respiration. Moreover, recent studies suggest that the carbon uptake period makes less contribution than the carbon uptake amplitude to IAV in NEE. Although land models incorporate most processes underlying IAV, their efficacy to predict the IAV in NEE remains low. Main conclusions To improve our ability to predict future IAV of the terrestrial C cycle, we have to understand biological mechanisms through which anomalies in climate factors cause the IAV of NEE. Future research needs to pay more attention not only to the differential effects of climate anomalies on photosynthesis and respiration but also to the relative importance of the C uptake period and amplitude in causing the IAV of NEE. Ultimately, we need multiple independent approaches, such as benchmark analysis, data assimilation and time‐series statistics, to integrate data, modelling frameworks and theory to improve our ability to predict future IAV in the terrestrial C cycle.

Car8 dorsal root ganglion expression and genetic regulation of analgesic responses are associated with a cis-eQTL in mice - Roy C. Levitt; Gerald Y. Zhuang; Yuan Kang; Diana M. Erasso; Udita Upadhyay; Mehtap Ozdemir; Eugene S. Fu; Konstantinos D. Sarantopoulos; Shad B. Smith; William Maixner; Luda Diatchenko; Eden R. Martin; et al. (Mammalian Genome, 2017)

Enhancement of Energy Production of the Intervertebral Disc by the Implantation of Polyurethane Mass Transfer Devices - Yu-Fu Wang; Howard B. Levene; Weiyong Gu; C. -Y. Charles Huang (Annals of Biomedical Engineering, 2017)

Reservoir characteristics and methane adsorption capacity of the Upper Triassic continental shale in Western Sichuan Depression, China - Y. C. Liu; D. X. Chen; N. S. Qiu; Y. Wang; J. Fu; Y. Huyan; J. K. Jia; H. Wu (Australian Journal of Earth Sciences, 2017)

Alterations in mechanical properties of the patellar tendon is associated with pain in athletes with patellar tendinopathy - W. C. Lee; Z. J. Zhang; L. Masci; G. Y. F. Ng; Siu Ngor Fu (European Journal of Applied Physiology, 2017)

Elements in Fine Particulate Matter (PM $$_{2.5}$$ 2.5 ) from Indoor Air During Household Stoves Coal Combustion at Xuanwei, China - K. H. Lui; C. S. Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Jinwen Li; Jun-Ji Cao; S. C. Lee; K. F. Ho (Aerosol Science and Engineering, 2017)

Differences between serum polar lipid profiles of male and female rheumatoid arthritis patients in response to glucocorticoid treatment - Junzeng Fu; Bart V. J. Cuppen; Paco M. J. Welsing; Herman van Wietmarschen; Amy C. Harms; Ruud Berger; Slavik Koval; Ruth D. E. Fritsch-Stork; Johannes W. J. Bijlsma; Thomas Hankemeier; Jan van der Greef; Floris P. J. G. Lafeber (Inflammopharmacology, 2016)

Time Course Field Analysis of COMT-Downregulated Switchgrass: Lignification, Recalcitrance, and Rust Susceptibility - Holly L. Baxter; Mitra Mazarei; Chunxiang Fu; Qunkang Cheng; Geoffrey B. Turner; Robert W. Sykes; Mark T. Windham; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (BioEnergy Research, 2016)

Impact of Partially Cemented and Non-persistent Natural Fractures on Hydraulic Fracture Propagation - Wei Fu; Brandon C. Ames; Andrew P. Bunger; Alexei A. Savitski (Rock Mechanics and Rock Engineering, 2016)

What caused the spring intensification and winter demise of the 2011 drought over Texas? - D. Nelun Fernando; Kingtse C. Mo; Rong Fu; Bing Pu; Adam Bowerman; Bridget R. Scanlon; Ruben S. Solis; Lei Yin; Robert E. Mace; John R. Mioduszewski; Tong Ren; Kai Zhang (Climate Dynamics, 2016)

Osteogenic Treatment Initiating a Tissue-Engineered Cartilage Template Hypertrophic Transition - J. Y. Fu; S. Y. Lim; P. F. He; C. J. Fan; D. A. Wang (Annals of Biomedical Engineering, 2016)

Smoking and Serum Lipid Profiles in Schizophrenia - Hui-Mei An; Yun-Long Tan; Shu-ping Tan; Jing Shi; Zhi-Ren Wang; Fu-De Yang; Xu-Feng Huang; Jair C. Soars; Thomas R. Kosten; Xiang-Yang Zhang (Neuroscience Bulletin, 2016)

Public health implications of social media use during natural disasters, environmental disasters, and other environmental concerns - Kathryn C. Finch; Kassandra R. Snook; Carmen H. Duke; King-Wa Fu; Zion Tsz Ho Tse; Atin Adhikari; Isaac Chun-Hai Fung (Natural Hazards, 2016)

Effect of Selenium Against Lead-Induced Damage on the Gene Expression of Heat Shock Proteins and Inflammatory Cytokines in Peripheral Blood Lymphocytes of Chickens - G.X. Sun; Y. Chen; C. P. Liu; S. Li; J. Fu (Biological Trace Element Research, 2016)

Effects of Dietary Selenium Against Lead Toxicity on mRNA Levels of 25 Selenoprotein Genes in the Cartilage Tissue of Broiler Chicken - H Gao; C. P. Liu; S. Q. Song; J. Fu (Biological Trace Element Research, 2016)

Characterization of pollution transport into Texas using OMI and TES satellite, GIS and in situ data, and HYSPLIT back trajectory analyses: implications for TCEQ State Implementation Plans - D. Bella; J. Culpepper; J. Khaimova; N. Ahmed; Adam Belkalai; I. Arroyo; J. Andrews; S. Gentle; S. Emmanuel; M. Lahmouh; J. Ealy; Zayna King; et al. (Air Quality, Atmosphere & Health, 2016)

Analyzing Economic and Environmental Performance of Switchgrass Biofuel Supply Chains - T. Edward Yu; Burton C. English; Lixia He; James A. Larson; James Calcagno; Joshua S. Fu; Brad Wilson (BioEnergy Research, 2016)

Thermal Drawdown-Induced Flow Channeling in Fractured Geothermal Reservoirs - Pengcheng Fu; Yue Hao; Stuart D. C. Walsh; Charles R. Carrigan (Rock Mechanics and Rock Engineering, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Effects of cigarette smoking and alcohol use on neurocognition and BDNF levels in a Chinese population - Xiang Yang Zhang; Yun-Long Tan; Da-Chun Chen; Shu-Ping Tan; Fu-De Yang; Giovana B. Zunta-Soares; Jair C Soares (Psychopharmacology, 2016)

Development of roughness updating based on artificial neural network in a river hydraulic model for flash flood forecasting - J C Fu; M H Hsu; Y Duann (Journal of Earth System Science, 2016)

The role of salinity in seed maturation of the euhalophyte Suaeda salsa - J. C. Zhou; T. T. Fu; N. Sui; J. R. Guo; G. Feng; J. L. Fan; J. Song (Plant Biosystems, 2016)

Catalytic behavior and synergistic effect of nonthermal plasma and CuO/AC catalyst for benzene destruction - C. He; L. Cao; X. Liu; W. Fu; J. Zhao (International Journal of Environmental Science and Technology, 2015)

Cloning, expression, and characterization of Pseudomonas vesicularis MA103 β-1,3-xylanase in Escherichia coli ClearColi BL21(DE3) - Wen-Sing Liang; Tsuei-Yun Fang; Hong-Ting Lin; Tristan C. Liu; Wen-Jung Lu; Wen-Shyong Tzou; Shye-Jye Tang; Fu-Pang Lin; Shiu-Mei Liu; Chorng-Liang Pan (Fisheries Science, 2015)

Production of transgenic beef cattle rich in n-3 PUFAs by somatic cell nuclear transfer - Gong Cheng; Changzhen Fu; Hong Wang; C. Adoligbe; Shengjuan Wei; Shijun Li; Bijie Jiang; Hongbao Wang; Linsen Zan (Biotechnology Letters, 2015)

Treating cutaneous aging with patented technologies - Wing-Fu Lai; Marie C Lin (Journal of Biosciences, 2015)

The Lhx9 homeobox gene controls pineal gland development and prevents postnatal hydrocephalus - Fumiyoshi Yamazaki; Morten Møller; Cong Fu; Samuel J. Clokie; Artem Zykovich; Steven L. Coon; David C. Klein; Martin F. Rath (Brain Structure and Function, 2015)

A Systematic Assessment of the Use of Platelet-Rich Plasma in Spinal Fusion - Benjamin D. Elder; Christina Holmes; C. Rory Goodwin; Sheng-Fu Lo; Varun Puvanesarajah; Thomas A. Kosztowski; John E. Locke; Timothy F. Witham (Annals of Biomedical Engineering, 2015)

Occurrence of triclosan in the tropical rivers receiving the effluents from the hospital wastewater treatment plant - Gordon C. C. Yang; Hsin-Jen Tsai; Fu-Kuei Chang (Environmental Monitoring and Assessment, 2015)

The role of heat shock proteins in oxidative stress damage induced by Se deficiency in chicken livers - C. P. Liu; J. Fu; F. P. Xu; X. S. Wang; S. Li (BioMetals, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

A novel fish cell line derived from the brain of Chinese perch Siniperca chuatsi : development and characterization - X. Fu; N. Li; Y. Lai; X. Luo; Y. Wang; C. Shi; Z. Huang; S. Wu; J. Su (Journal of Fish Biology, 2015)
In this study, a continuous cell line (named as CPB ) was established from Siniperca chuatsi brain and has been subcultured >140 times. CPB cell line predominantly consisted of fibroblast‐like cells that could grow better in Leibovitz's L‐15 supplemented with 10% foetal bovine serum at 28° C. Polymerase chain reaction amplification of 18s recombinant (r)RNA confirmed the origin of this cell line from S. chuatsi . The CPB cell line was cryopreserved at different passage levels and revived successfully with 80–90% survival. The cell line was further characterized by chromosome number and transfection. The CPB cells were highly susceptible to infectious spleen and kidney necrosis virus ( ISKNV ) with a titre of 6·58–6·62 log TCID 50 ml −1 and numerous ISKNV particles were observed in the cytoplasm by transmission electron microscopy. At the same time, ISKNV infection was confirmed by reverse transcriptase polymerase chain reaction, immunodot blot and individual challenge experiments. The development and characterization of a new brain cell line from S. chuatsi were described in this study and it could be used as an in vitro tool for propagation of ISKNV and gene expression studies.

Quantitative trait analysis of flowering time in spring rapeseed (B. napus L.) - Y. X. Luo; C. Y. Luo; D. Z. Du; Z. Fu; Y. M. Yao; C. C. Xu; H. S. Zhang (Euphytica, 2014)

The Development of Drug-Free Therapy for Prevention of Dental Caries - Fu Chen; Zhenshan Jia; Kelly C. Rice; Richard A. Reinhardt; Kenneth W. Bayles; Dong Wang (Pharmaceutical Research, 2014)

Assessing scalar concentration footprint climatology and land surface impacts on tall-tower CO2 concentration measurements in the boreal forest of central Saskatchewan, Canada - Baozhang Chen; Huifang Zhang; Nicholas C. Coops; Dongjie Fu; Douglas E. J. Worthy; Guang Xu; T. Andy Black (Theoretical and Applied Climatology, 2014)

Effects of Dietary Selenium Deficiency on mRNA Levels of Twenty-One Selenoprotein Genes in the Liver of Layer Chicken - C. P. Liu; J. Fu; S. L. Lin; X. S. Wang; S. Li (Biological Trace Element Research, 2014)

Exploring the role of a stigma-expressed plant U-box gene in the pollination responses of transgenic self-incompatible Arabidopsis thaliana - Jianfeng Zhang; Anne C. Rea; Tingdong Fu; Chaozhi Ma; June B. Nasrallah (Plant Reproduction, 2014)

Comparative genotype reactions to Sclerotinia sclerotiorum within breeding populations of Brassica napus and B. juncea from India and China - M. J. Barbetti; S. K. Banga; T. D. Fu; Y. C. Li; D. Singh; S. Y. Liu; X. T. Ge; S. S. Banga (Euphytica, 2014)

Intraperitoneal delivery of paclitaxel by poly(ether-anhydride) microspheres effectively suppresses tumor growth in a murine metastatic ovarian cancer model - Ming Yang; Tao Yu; Joseph Wood; Ying-Ying Wang; Benjamin C. Tang; Qi Zeng; Brian W. Simons; Jie Fu; Chi-Mu Chuang; Samuel K. Lai; T.-C. Wu; Chien-Fu Hung; et al. (Drug Delivery and Translational Research, 2014)

Re–Os isotope and platinum-group element geochemistry of the Pobei Ni–Cu sulfide-bearing mafic–ultramafic complex in the northeastern part of the Tarim Craton - Sheng-Hong Yang; Mei-Fu Zhou; Peter C. Lightfoot; Ji-Feng Xu; Christina Yan Wang; Chang-Yi Jiang; Wen-Jun Qu (Mineralium Deposita, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Toxic effects of hexaflumuron on the development of Coccinella septempunctata - Caihong Yu; Maoran Fu; Ronghua Lin; Yan Zhang; Liu Yongquan; Hui Jiang; Theo C. M. Brock (Environmental Science and Pollution Research, 2014)

The Development of Dentotropic Micelles with Biodegradable Tooth-Binding Moieties - Fu Chen; Zhenshan Jia; Kelly C. Rice; Richard A. Reinhardt; Kenneth W. Bayles; Dong Wang (Pharmaceutical Research, 2013)

Histone deacetylase inhibitor AR-42 enhances E7-specific CD8+ T cell-mediated antitumor immunity induced by therapeutic HPV DNA vaccination - Sung Yong Lee; Zhuomin Huang; Tae Heung Kang; Ruey-Shyang Soong; Jayne Knoff; Ellen Axenfeld; Chenguang Wang; Ronald D. Alvarez; Ching-Shih Chen; Chien-Fu Hung; T.-C. Wu (Journal of Molecular Medicine, 2013)

Superparamagnetic Iron Oxide is Suitable to Label Tendon Stem Cells and Track Them In Vivo with MR Imaging - Yunfa Yang; Jianying Zhang; Yongxian Qian; Shiwu Dong; He Huang; Fernando E. Boada; Freddie H. Fu; James H-C. Wang (Annals of Biomedical Engineering, 2013)

Distribution of platinum-group elements in magmatic and altered ores in the Jinchuan intrusion, China: an example of selenium remobilization by postmagmatic fluids - Hazel M. Prichard; Robert D. Knight; Peter C. Fisher; Iain McDonald; Mei-Fu Zhou; Christina Y. Wang (Mineralium Deposita, 2013)

Sequence organization and evolutionary dynamics of Brachypodium-specific centromere retrotransposons - L. L. Qi; J. J. Wu; B. Friebe; C. Qian; Y. Q. Gu; D. L. Fu; B. S. Gill (Chromosome Research, 2013)

Improvement of short-term forecasting in the northwest Pacific through assimilating Argo data into initial fields - Hongli Fu; Peter C. Chu; Guijun Han; Zhongjie He; Wei Li; Xuefeng Zhang (Acta Oceanologica Sinica, 2013)

Standardization of Switchgrass Sample Collection for Cell Wall and Biomass Trait Analysis - C. Frank Hardin; Chunxiang Fu; Hiroshi Hisano; Xirong Xiao; Hui Shen; C. Neal Stewart; Wayne Parrott; Richard A. Dixon; Zeng-Yu Wang (BioEnergy Research, 2013)

Scl gene construction, expression and effect on hemangioma - H. X. Yin; Z. H. Zhang; J. C. Shen; A. L. Zhang; T. Y. Zhang; J. X. Luo; C. Y. Fu; X. P. Yi; Z. W. Liu; S. S. Yang; B. Zhou; X. Fu (Molecular Biology Reports, 2013)

Evaluation and QTL mapping of phosphorus concentration in soybean seed - Keith E. King; Nick Lauter; Shun Fu Lin; M. Paul Scott; Randy C. Shoemaker (Euphytica, 2013)

Real-time multivariate indices for the boreal summer intraseasonal oscillation over the Asian summer monsoon region - June-Yi Lee; Bin Wang; Matthew C. Wheeler; Xiouhua Fu; Duane E. Waliser; In-Sik Kang (Climate Dynamics, 2013)

Heterogeneous Os isotope compositions in the Kalatongke sulfide deposit, NW China: the role of crustal contamination - Jian-Feng Gao; Mei-Fu Zhou; Peter C. Lightfoot; Wenjun Qu (Mineralium Deposita, 2012)

Hydrocarbon- and ore-bearing basinal fluids: a possible link between gold mineralization and hydrocarbon accumulation in the Youjiang basin, South China - X. X. Gu; Y. M. Zhang; B. H. Li; S. Y. Dong; C. J. Xue; S. H. Fu (Mineralium Deposita, 2012)

Timing of gold mineralisation in the western Lachlan Orogen, SE Australia: A critical overview - D. Phillips; B. Fu; C. J.L. Wilson; M. A. Kendrick; A. M. Fairmaid; J. MCL. Miller (Australian Journal of Earth Sciences, 2012)

Constitutive expression of barley α-amylase in Pichia pastoris by high-density cell culture - Z. W. Liu; H. X. Yin; X. P. Yi; A. L. Zhang; J. X. Luo; T. Y. Zhang; C. Y. Fu; Z. H. Zhang; J. C. Shen; L. P. Chen (Molecular Biology Reports, 2012)

Association between ATM 5557G>A polymorphism and breast cancer risk: a meta-analysis - Chen Mao; Vincent C. H. Chung; Ben-Fu He; Rong-Cheng Luo; Jin-Ling Tang (Molecular Biology Reports, 2012)

Erratum to: Genetic analysis of Down syndrome-associated heart defects in mice - Chunhong Liu; Masae Morishima; Tao Yu; Sei-Ichi Matsui; Li Zhang; Dawei Fu; Annie Pao; Alberto C. Costa; Katheleen J. Gardiner; John K. Cowell; Norma J. Nowak; Michael S. Parmacek; et al. (Human Genetics, 2011)

Genetic analysis of Down syndrome-associated heart defects in mice - Chunhong Liu; Masae Morishima; Tao Yu; Sei-Ichi Matsui; Li Zhang; Dawei Fu; Annie Pao; Alberto C. Costa; Katheleen J. Gardiner; John K. Cowell; Normal J. Nowak; Michael S. Parmacek; et al. (Human Genetics, 2011)

Numerical simulation of fluxes generated by inhomogeneities of the underlying surface over the Jinta Oasis in Northwestern China - Wanli Li; Shihua Lü; Shenming Fu; Xianhong Meng; H. C. Nnamchi (Advances in Atmospheric Sciences, 2011)

Activation of group IVC phospholipase A2 by polycyclic aromatic hydrocarbons induces apoptosis of human coronary artery endothelial cells - Patricia K. Tithof; Sean M. Richards; Mona A. Elgayyar; Fu-Minn Menn; Vijay M. Vulava; Larry McKay; John Sanseverino; Gary Sayler; Dawn E. Tucker; Christina C. Leslie; Kim P. Lu; Kenneth S. Ramos (Archives of Toxicology, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Saturnispora serradocipensis sp. nov. and Saturnispora gosingensis sp. nov., two ascomycetous yeasts from ephemeral habitats - Monica R. Canelhas; Anne C. Barbosa; Adriana O. Medeiros; Ching-Fu Lee; Li-Yin Huang; Marc-André Lachance; Carlos A. Rosa (Antonie van Leeuwenhoek, 2011)

Dietary patterns and breast cancer risk among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Jian-Hua Fu; Shou-Zhen Cheng; Yu-Ming Chen; Fang-Yu Lin (Cancer Causes & Control, 2011)

Triclosan-Loaded Tooth-Binding Micelles for Prevention and Treatment of Dental Biofilm - Fu Chen; Kelly C. Rice; Xin-Ming Liu; Richard A. Reinhardt; Kenneth W. Bayles; Dong Wang (Pharmaceutical Research, 2010)

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

OSTM/Jason-2: Assessment of the System Performances (Ocean Surface Topography Mission: OSTM) - G. Zaouche; J. Perbos; T. Lafon; V. Couderc; J. Lambin; J. D. Desjonqueres; C. Jayles; E. Jurado; P. Vaze; L.-L. Fu; S. Brown; F. Parisot; et al. (Marine Geodesy, 2010)

How are seasonal prediction skills related to models’ performance on mean state and annual cycle? - June-Yi Lee; Bin Wang; I.-S. Kang; J. Shukla; A. Kumar; J.-S. Kug; J. K. E. Schemm; J.-J. Luo; T. Yamagata; X. Fu; O. Alves; B. Stern; et al. (Climate Dynamics, 2010)

Conservation and development through medicinal plants: a case study from Ludian (Northwest Yunnan, China) and presentation of a general model - Pei Shengji; Alan C. Hamilton; Yang Lixin; Huai Huyin; Yang Zhiwei; Gao Fu; Zhang Quangxin (Biodiversity and Conservation, 2010)

Therapeutic HPV DNA vaccines - Ken Lin; Elena Roosinovich; Barbara Ma; Chien-Fu Hung; T.-C. Wu (Immunologic Research, 2010)

Chromosomal evolution of Arvicolinae (Cricetidae, Rodentia). III. Karyotype relationships of ten Microtus species - Natalia A. Lemskaya; Svetlana A. Romanenko; Feodor N. Golenishchev; Nadezhda V. Rubtsova; Olga V. Sablina; Natalya A. Serdukova; Patricia C. M. O’Brien; Beiyuan Fu; Nuri Yiğit; Malcolm A. Ferguson-Smith; Fengtang Yang; Alexander S. Graphodatsky (Chromosome Research, 2010)

Development of delivery methods for carbohydrate-based drugs: controlled release of biologically-active short chain fatty acid-hexosamine analogs - Udayanath Aich; M. Adam Meledeo; Srinivasa-Gopalan Sampathkumar; Jie Fu; Mark B. Jones; Christopher A. Weier; Sung Yun Chung; Benjamin C. Tang; Ming Yang; Justin Hanes; Kevin J. Yarema (Glycoconjugate Journal, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Tissue Distribution of Polybrominated Diphenyl Ethers (PBDEs) in Captive Domestic Pigs, Sus scrofa, from a Village Near an Electronic Waste Recycling Site in South China - Y. F. Li; Z. Z. Yang; C. H. Wang; Z. J. Yang; Z. F. Qin; S. Fu (Bulletin of Environmental Contamination and Toxicology, 2010)

Meat and egg consumption and risk of breast cancer among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Yu-Ming Chen; Fang-Yu Lin; Jian-Hua Fu; Shou-Zhen Cheng (Cancer Causes & Control, 2009)

A revised method of presenting wavenumber–frequency power spectrum diagrams that reveals the asymmetric nature of tropical large-scale waves - Winston C. Chao; Bo Yang; Xiouhua Fu (Climate Dynamics, 2009)

Effect of polymorphism in the leukemia inhibitory factor gene on litter size in Large White pigs - H. C. Lin; G. F. Liu; A. G. Wang; L. J. Kong; X. F. Wang; J. L. Fu (Molecular Biology Reports, 2009)

Phylogeographical analysis of an estuarine fish, Salanx ariakensis (Osmeridae: Salanginae) in the north‐western Pacific - X. Hua; W. Wang; W. Yin; Q. He; B. Jin; J. Li; J. Chen; C. Fu (Journal of Fish Biology, 2009)
This study extended the geographic coverage of a previous study to explore population genetic structure and demographic history in the Ariake icefish Salanx ariakensis from three populations of continental coastlines and one island population in the north‐western Pacific based on a partial sequence of the mitochondrial cytochrome b gene. The S. ariakensis showed high genetic diversity and strong genetic structure. Phylogenetic analysis showed a shallow gene tree with no clear phylogeographical structure. Contiguous range expansion and restricted gene flow were inferred to be main population events by nested‐clade analysis. Significant genetic differentiations between populations could be attributable to negligible gene flow by coalescent analysis. High nucleotide diversity of each population was due to geographic mixing of heterogenous haplotypes during lowering sea levels of the Pleistocene. These findings indicate that cycles of geographic isolation and secondary contact happened in the Pleistocene glacial–interglacial cycles shaping genetic structure and population demography of S. ariakensis .

Advance and prospectus of seasonal prediction: assessment of the APCC/CliPAS 14-model ensemble retrospective seasonal prediction (1980–2004) - Bin Wang; June-Yi Lee; In-Sik Kang; J. Shukla; C.-K. Park; A. Kumar; J. Schemm; S. Cocke; J.-S. Kug; J.-J. Luo; T. Zhou; B. Wang; et al. (Climate Dynamics, 2009)

Avian comparative genomics: reciprocal chromosome painting between domestic chicken (Gallus gallus) and the stone curlew (Burhinus oedicnemus, Charadriiformes)—An atypical species with low diploid number - Wenhui Nie; Patricia C. M. O’Brien; Bee L. Ng; Beiyuan Fu; Vitaly Volobouev; Nigel P. Carter; Malcolm A. Ferguson-Smith; Fengtang Yang (Chromosome Research, 2009)

Reduced swimming abilities in fast‐growing transgenic common carp Cyprinus carpio associated with their morphological variations - D. Li; W. Hu; Y. Wang; Z. Zhu; C. Fu (Journal of Fish Biology, 2009)
Critical swimming speeds ( U crit ) and morphological characters were compared between the F 4 generation of GH‐transgenic common carp Cyprinus carpio and the non‐transgenic controls. Transgenic fish displayed a mean absolute U crit value 22·3% lower than the controls. Principal component analysis identified variations in body shape, with transgenic fish having significantly deeper head, longer caudal length of the dorsal region, longer standard length ( L S ) and shallower body and caudal region, and shorter caudal length of the ventral region. Swimming speeds were related to the combination of deeper body and caudal region, longer caudal length of the ventral region, shallower head depth, shorter caudal length of dorsal region and L S . These findings suggest that morphological variations which are poorly suited to produce maximum thrust and minimum drag in GH‐transgenic C. carpio may be responsible for their lower swimming abilities in comparison with non‐transgenic controls.

Platinum-group minerals from the Jinbaoshan Pd–Pt deposit, SW China: evidence for magmatic origin and hydrothermal alteration - Christina Yan Wang; Hazel M. Prichard; Mei-Fu Zhou; Peter C. Fisher (Mineralium Deposita, 2008)

Simulation of direct effects of black carbon aerosol on temperature and hydrological cycle in Asia by a Regional Climate Model - J. Wu; C. Fu; Y. Xu; J. P. Tang; W. Wang; Z. Wang (Meteorology and Atmospheric Physics, 2008)

Treatment with proteasome inhibitor bortezomib enhances antigen-specific CD8+ T-cell-mediated antitumor immunity induced by DNA vaccination - Chih-Wen Tseng; Archana Monie; Chao-Yi Wu; Bruce Huang; Mei-Cheng Wang; Chien-Fu Hung; T.-C. Wu (Journal of Molecular Medicine, 2008)

Multidirectional cross-species painting illuminates the history of karyotypic evolution in Perissodactyla - Vladimir A. Trifonov; Roscoe Stanyon; Anastasia I. Nesterenko; Beiyuan Fu; Polina L. Perelman; Patricia C M O’Brien; Gary Stone; Nadezhda V. Rubtsova; Marlys L. Houck; Terence J. Robinson; Malcolm A. Ferguson-Smith; Gauthier Dobigny; et al. (Chromosome Research, 2008)

Response of Brassica napus and B. juncea germplasm from Australia, China and India to Australian populations of Leptosphaeria maculans - C. X. Li; N. Wratten; P. A. Salisbury; W. A. Burton; T. D. Potter; G. Walton; Hua Li; K. Sivasithamparam; Surinder S. Banga; Shashi Banga; D. Singh; S. Y. Liu; et al. (Australasian Plant Pathology, 2008)

Hedgehog signaling in the murine melanoma microenvironment - Ling Geng; Kyle C. Cuneo; Michael K. Cooper; Hong Wang; Konjeti Sekhar; Allie Fu; Dennis E. Hallahan (Angiogenesis, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Fast‐growing transgenic common carp mounting compensatory growth - C. Fu; D. Li; W. Hu; Y. Wang; Z. Zhu (Journal of Fish Biology, 2007)
Compensatory growth is a phase of accelerated growth apparent when favourable conditions are restored after a period of growth depression. To investigate if F 2 common ‘all‐fish’ growth hormone gene transgenic common carp ( Cyprinus carpio ) could mount compensatory growth, a 9 week study at 29° C was performed. The control group was fed to satiation twice a day throughout the experiment. The other two groups were deprived of feed for 1 or 2 weeks, respectively, and then fed to satiation during the re‐feeding period. At the end of the experiment, the live masses of fish in the deprived groups were still significantly lower than those of the controls. During the re‐feeding period, size‐adjusted mean specific growth rates and mean feed intakes were significantly higher in the deprived fish than in the controls, indicating a partial compensatory growth response in these fish. No significant differences were found in food conversion efficiency between the deprived and control fish during re‐feeding, suggesting that hyperphagia was the mechanism responsible for increased growth rates. The proximate composition of the deprived fish at the end of the experiment was similar to that of the control fish. This study is, to our knowledge, the first to report that fast‐growing transgenic fish can achieve partial compensation of growth following starvation.

Two new flavanes and bioactive compounds from Daphne tangutica Maxim - W. Zhang; Y. H. Shen; Z. Y. Lou; R. H. Liu; C. Zhang; P. Fu; L. Shan; W. D. Zhang (Natural Product Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Chromosomal evolution of Arvicolinae (Cricetidae, Rodentia). I. The genome homology of tundra vole, field vole, mouse and golden hamster revealed by comparative chromosome painting - Natalia A. Sitnikova; Svetlana A. Romanenko; Patricia C. M. O’Brien; Polina L. Perelman; Beiyuan Fu; Nadezhda V. Rubtsova; Natalya A. Serdukova; Feodor N. Golenishchev; Vladimir A. Trifonov; Malcolm A. Ferguson-Smith; Fengtang Yang; Alexander S. Graphodatsky (Chromosome Research, 2007)

Composition and antimicrobial activity of the essential oil of Actinidia macrosperma from China - Y. Lu†; Y. P. Zhao†; Z. C. Wang; S. Y. Chen; C. X. Fu* (Natural Product Research, 2007)

Sesquiterpene lactones from Saussurea alata - G. Ren; Z. M. Yu; Y. L. Chen; S. H. Wu; C. X. Fu (Natural Product Research, 2007)

Growth and energy budget of F 2 ‘all‐fish’ growth hormone gene transgenic common carp - C. Fu; D. Li; W. Hu; Y. Wang; Z. Zhu (Journal of Fish Biology, 2007)
The growth and energy budget for F 2 ‘all‐fish’ growth hormone gene transgenic common carp Cyprinus carpio of two body sizes were investigated at 29·2° C for 21 days. Specific growth rate, feed intake, feed efficiency, digestibility coefficients of dry matter and protein, gross energy intake ( I E ), and the proportion of I E utilized for heat production ( H E ) were significantly higher in the transgenics than in the controls. The proportion of I E directed to waste products [faecal energy ( F E ) and excretory energy loss ( Z E + U E ) where Z E is through the gills and U E through the kidney], and the proportion of metabolizable energy ( M E ) for recovered energy ( R E ) were significantly lower in the transgenics than in the controls. The average energy budget equation of transgenic fish was as follows: 100 I E = 19·3 F E + 6·0 ( Z E + U E ) + 45·2 H E + 29·5 R E or 100 M E = 60·5 H E + 39·5 R E . The average energy budget equation of the controls was: 100 I E = 25·2 F E + 7·4 ( Z E + U E ) + 35·5 H E + 31·9 R E or 100 M E = 52·7 H E + 47·3 R E . These findings indicate that the high growth rate of ‘all‐fish’ transgenic common carp relative to their non‐transgenic counterparts was due to their increased feed intake, reduced lose of waste productions and improved feed efficiency. The benefit of the increased energy intake by transgenic fish, however, was diminished by their increased metabolism.

Octad pollen formation in Cymbopetalum (Annonaceae): the binding mechanism - C. -H. Tsou; Y. -L. Fu (Plant Systematics and Evolution, 2007)

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Expression of α-dystrobrevin in blood-tissue barriers: sub-cellular localisation and molecular characterisation in normal and dystrophic mice - Chun Fu Lien; Diana Hazai; Davy Yeung; Juraini Tan; Ernst-Martin Füchtbauer; Veronika Jancsik; Dariusz C. Górecki (Cell and Tissue Research, 2006)

The systematic value of pollen morphology in Smilacaceae - S.-C. Chen; X.-P. Zhang; S.-F. Ni; C.-X. Fu; K. M. Cameron (Plant Systematics and Evolution, 2006)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

Restoration of Marine Coastal Ecosystem Health as a New Goal for Integrated Catchment Management in Tolo Harbor, Hong Kong, China - Fu-Liu Xu; Jun-Yi Hao; Shu Tao; Richard W. Dawson; K. C. Lam; Yongqin David Chen (Environmental Management, 2006)

A Modified Cyclic Cracking Model for RC Structural Walls Behaviour Under Dynamic Excitation - Tsai-Fu Chuang; Andrew H. C. Chan; Les A. Clark (Bulletin of Earthquake Engineering, 2005)

Effects of ketamine on prefrontal and striatal regions in an overt verbal fluency task: a functional magnetic resonance imaging study - Cynthia H. Y. Fu; Kathryn M. Abel; Matthew P. G. Allin; David Gasston; Sergi G. Costafreda; John Suckling; Steve C. R. Williams; Philip K. McGuire (Psychopharmacology, 2005)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Sleep-related vagotonic effect of zolpidem in rats - Hsiao Ying Chen; Terry B. J. Kuo; Fu-Zen Shaw; Ching J. Lai; Cheryl C. H. Yang (Psychopharmacology, 2005)

Genome-wide Introgression Lines and their Use in Genetic and Molecular Dissection of Complex Phenotypes in Rice (Oryza sativa L.) - Zhi-Kang Li; Bin-Ying Fu; Yong-Ming Gao; Jian-Long Xu; J. Ali; H. R. Lafitte; Yun-Zhu Jiang; J. Domingo Rey; C. H. M. Vijayakumar; R. Maghirang; Tian-Qing Zheng; Ling-Hua Zhu (Plant Molecular Biology, 2005)

Mercury Accumulation and Distribution in Medaka after the Exposure to Sublethal Levels of Methylmercury - C.-Y. Liao; Q.-F. Zhou; J.-B. Shi; J.-J. Fu; G.-B. Jiang (Bulletin of Environmental Contamination and Toxicology, 2005)

Single and multiple congenic strains for hydrocephalus in the H-Tx rat - Hazel C. Jones; Gin-Fu Chen; Baligh R. Yehia; Barbara J. Carter; Elizabeth J. Akins; Logan C. Wolpin (Mammalian Genome, 2005)

Simulation Studies of High-Latitude Magnetospheric Boundary Dynamics - Q. Q. Shi; Z. Y. Pu; H. Zhang; S. Y. Fu; C. J. Xiao; Q. -G. Zong; T. A. Fritz; Z. X. Liu (Surveys in Geophysics, 2005)

Energetic Particles Observed in the CUSP Region During a Storm Recovery Phase - S. Y. Fu; Q. G. Zong; Z. Y. Pu; C. J. Xiao; A. Korth; P. Daly; H. Reme (Surveys in Geophysics, 2005)

Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 - Z. Y. Pu; Q. -G. Zong; T. A. Fritz; C. J. Xiao; Z. Y. Huang; S. Y. Fu; Q. Q. Shi; M. W. Dunlop; K. -H. Glassmeier; A. Balogh; P. Daly; H. Reme; et al. (Surveys in Geophysics, 2005)

Glycoprotein-mediated induction of apoptosis limits the spread of attenuated rabies viruses in the central nervous system of mice - Luciana Sarmento; Xia-qing Li; Elizabeth Howerth; Alan C. Jackson; Zhen F. Fu (Journal of NeuroVirology, 2005)

GISH, AFLP and PCR-RFLP analysis of an intergeneric somatic hybrid combining Goutou sour orange and Poncirus trifoliata - C. H. Fu; C. L. Chen; W. W. Guo; X. X. Deng (Plant Cell Reports, 2004)

Analyses of cis -acting elements that affect the transposition of Mos1 mariner transposons in vivo - D. W. Pledger; Y. Q. Fu; C. J. Coates (Molecular Genetics and Genomics, 2004)

Amazonian climate: results and future research - J. H. C. Gash; C. Huntingford; J. A. Marengo; R. A. Betts; P. M. Cox; G. Fisch; R. Fu; A. W. Gandu; P. P. Harris; L. A. T. Machado; C. von Randow; M. A. Silva Dias (Theoretical and Applied Climatology, 2004)

Evolution of Genome Organizations of Squirrels (Sciuridae) Revealed by Cross-Species Chromosome Painting - Tangliang Li; Patricia C. M. O'Brien; Larisa Biltueva; Beiyuan Fu; Jinhuan Wang; Wenhui Nie; Malcolm A. Ferguson-Smith; Alexander S. Graphodatsky; Fengtang Yang (Chromosome Research, 2004)

Refined genome-wide comparative map of the domestic horse, donkey and human based on cross-species chromosome painting: insight into the occasional fertility of mules - Fengtang Yang; Beiyuan Fu; Patricia C. M. O'Brien; Wenhui Nie; Oliver A. Ryder; Malcolm A. Ferguson-Smith (Chromosome Research, 2004)

Molecular diversity and multilocus organization of the parental lines used in the International Rice Molecular Breeding Program - S. B. Yu; W. J. Xu; C. H. M. Vijayakumar; J. Ali; B. Y. Fu; J. L. Xu; Y. Z. Jiang; R. Marghirang; J. Domingo; C. Aquino; S. S. Virmani; Z. K. Li (Theoretical and Applied Genetics, 2003)

Regeneration of citrus sinensis (+) clausena lansium intergeneric triploid and tetraploid somatic hybrids and their identification by molecular markers - C. H. Fu; W. W. Guo; J. H. Liu; X. X. Deng (In Vitro Cellular & Developmental Biology - Plant, 2003)

Attenuated Lapinized Chinese Strain of Classical Swine Fever Virus: Complete Nucleotide Sequence and Character of 3′-Noncoding Region - H. X. Wu; J. F. Wang; C. Y. Zhang; L. Z. Fu; Z. S. Pan; N. Wang; P. W. Zhang; W. G. Zhao (Virus Genes, 2001)

Comparison of the postprandial release of peptide YY and proglucagon-derived peptides in the rat - Younes Anini; Xiaomei Fu-Cheng; Jean Claude Cuber; Alain Kervran; Jacques Chariot; C. Roz (Pflügers Archiv - European Journal of Physiology, 1999)

The barriers to bluetongue virus infection, dissemination and transmission in the vector, Culicoides variipennis (Diptera: Ceratopogonidae) - H. Fu; C. J. Leake; P. P. C. Mertens; P. S. Mellor (Archives of Virology, 1999)

Tissue- and stage-specific expression of a soybean (Glycine max L.) seed-maturation, biotinylated protein - Yue-ie C. Hsing; Chih-hua Tsou; Tze-fu Hsu; Zuey-ying Chen; Kim-leong Hsieh; Jaw-shu Hsieh; Teh-yuan Chow (Plant Molecular Biology, 1998)

Growth and feed utilization by F 4 human growth hormone transgenic carp fed diets with different protein levels - C. Fu; Y. Cui; S. S. O. Hung; Z. Zhu (Journal of Fish Biology, 1998)
The F 4 generation of human growth hormone (hGH) transgenic red common carp Cyprinus carpio had significantly higher growth rates than the non‐transgenic controls. Protein and energy intakes were significantly higher in the transgenic carp than in the controls fed the 20% protein diet, but were not different between the two strains fed diets with 30 and 40% protein. Faecal protein loss, as a proportion of protein intake, was significantly lower in the transgenics than in the controls fed diets with 20 and 30% protein, but was not different between the two strains fed diet with 40% protein. Faecal energy loss, as a proportion of energy intake, was significantly lower in the transgenics than in the controls fed diet with 20% protein, but was not different between the two strains fed diets with 30 and 40% protein. Recovered protein, as a proportion of protein intake, was significantly higher in the transgenics than in the controls fed all diets, whereas recovered energy was significantly higher in the transgenic fish fed the 40% protein diet. For fish fed each diet, the transgenics had significantly higher body contents of dry matter and protein, but lower contents of lipid than the controls. It was concluded that transgenics were more efficient in utilizing dietary protein than the controls. At a lower dietary protein level, transgenics achieved higher growth rates mainly by increasing feed intake; at higher levels of dietary protein, transgenics achieved higher growth rates mainly through a higher energy conversion efficiency.

Retroviral gene transfer for the assignment of Fanconi anemia (FA) patients to a FA complementation group - Kai-Ling Fu; Peter C. Thuß; Tadahiro Fujino; Martin Digweed; Johnson M. Liu; Christopher E. Walsh (Human Genetics, 1998)

Heterogeneous cellular expression of creatine kinase isoenzyme during normal rat heart development - Russell T. Dowell; May C. Fu (Molecular and Cellular Biochemistry, 1998)

Molecular indicators of microbial contributions to recent and Tertiary hypersaline lacustrine sediments in China - Ruiliang Wang; Simon C. Brassell; Jiamo Fu; Guoying Sheng (Hydrobiologia, 1998)

Angiotensin II receptors: Localization of type I and type II in rat epididymides of different developmental stages - P. S. Leung; H. C. Chan; L. X. M. Fu; P. Y. Leung; S. B. C. Chew; P. Y. D. Wong (The Journal of Membrane Biology, 1997)

Mechanisms of peptide YY release induced by an intraduodenal meal in rats: neural regulation by proximal gut - Xiaomei Fu-Cheng; Younes Anini; Jacques Chariot; Nathalie Castex; Jean-Paul Galmiche; C. Rozé (Pflügers Archiv - European Journal of Physiology, 1997)

Case 23 nomination of precursory seismic quiescence as a significant precursor - Max Wyss; R. E. Habermann; P. Bodin; Carl Kisslinger; R. O. Burford; F. W. Klein; A. C. Johnson; Zhengxiang Fu (Pure and Applied Geophysics, 1997)

Effect of waterborne and dietary cadmium on plasma ions of the teleostOreochromis mossambicus in relation to water calcium levels - H. B. Pratap; H. Fu; R. A. C. Lock; S. E. Wendelaar Bonga (Archives of Environmental Contamination and Toxicology, 1989)